Manufacturing method of plate-shaped molded product

JP2025023813APending Publication Date: 2025-02-17ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024098295
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-04
Filing Date
2024-06-18
Publication Date
2025-02-17

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、成形品の黄変、外観不良及び反りが低減された、一方の主面に微細な凸形状を有する板状成形品を製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023813000007
    Figure 2025023813000007
  • Figure 2025023813000008
    Figure 2025023813000008
  • Figure 2025023813000009
    Figure 2025023813000009
Patent Text Reader

Abstract

To provide a manufacturing method of a plate-shaped molded product, which can reduce yellowing, poor appearance and warpage of the molded product even if the plate-shaped molded product has a fine convex shape on one of its main surfaces and has a large projection area of the main surface.SOLUTION: There is provided a manufacturing method of a plate-shaped molded product that includes a methacrylic resin composition having a glass transition temperature Tg of 115 to 160°C and a melt viscosity of 20 to 235 Pa sec at 270°C and 1000 sec-1, has no adhesive interface, and is composed of a single resin composition. One of its main surface (first main surface) of the plate-shaped molded product has a plurality of fine convex shapes, and the other of the main surfaces (second main surface) is a flat surface, the convex shape has a height a of 0.5 to 600 μm and a ratio b / a of a pitch b to the height a of 0.1 to 2.0, and a projection area of the first main surface is 225 cm2 or more. The manufacturing method includes injection molding using a first mold on the first main surface side and a second mold on the second main surface side. The maximum temperature Tmax of the first mold is set between (Tg+40)°C and (Tg+70)°C, and the temperature of the second mold is set between (Tmax-90)°C and (Tmax-65)°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a plate-shaped molded product having fine protrusions on one of its main surfaces. [Background technology]

[0002] Conventionally, in the molding of injection-molded products having fine uneven shapes, an injection molding method has been used in which the entire surface of the mold cavity in contact with the molded product is heated in advance to a set value equal to or higher than the softening temperature of the resin, and the set value is controlled to be maintained during the injection process, and when the cooling process is started, the heating is completed and the mold is cooled. In such an injection molding method, by heating the mold cavity surface to a set value equal to or higher than the softening temperature of the resin before the injection process starts, it is possible to reduce residual stress and solve molding defects such as deformation, cracks, and deterioration of birefringence (for example, Patent Documents 1 to 6). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-80940 [Patent Document 2] Japanese Patent Application Publication No. 10-80938 [Patent Document 3] Japanese Patent Application Publication No. 11-58476 [Patent Document 4] Japanese Patent Application Publication No. 63-95919 [Patent Document 5] JP 2010-264703 A [Patent Document 6] JP 2023-013970 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, when a mold having a mechanism for heating and cooling only the fine shape forming surface of the mold is used, a temperature difference occurs between the forming surface side and the flat surface facing it, and the molded product often warps during the cooling process. In particular, when the molded product is used for optical purposes, there is a problem that the shape and warping of the molded product adversely affect the optical properties.

[0005] The above-mentioned Patent Document 6 reports a method for simultaneously controlling the appearance defects and warpage of a molded product by using a mold in which the cavity surface is heated to a load deflection temperature or higher by a heat transfer heater wire near the cavity surface and then cooled with water when manufacturing a plate-shaped molded product having a fine convex shape on one main surface, and controlling the temperature of the mold surface forming the fine convex shape and the mold surface facing it. However, the above-mentioned Patent Document 6 only considers molded products having a main surface having a fine convex shape with a length of 90 mm and a width of 90 mm. When the size (projected area) of the main surface having a fine convex shape becomes large, there is a problem that transfer failure of the fine convex shape and yellowing of the molded product may occur near the flow end, and a molded product with a good appearance may not be obtained. In particular, when a molded product having a large projected area of ​​the main surface having a fine convex shape is molded using a resin with a high melt viscosity, transfer failure of the fine convex shape tends to be significant. Furthermore, the inventors' investigations have revealed that when the projected area of ​​the main surface having a fine convex shape becomes large, warping of the molded product may not be sufficiently suppressed even if the mold temperature is controlled within the mold temperature range described in Patent Document 6.

[0006] The present invention has been made in consideration of the above-mentioned problems, and has an object to provide a method for producing a plate-shaped molded product that can reduce yellowing, poor appearance, and warping of the molded product, even if the plate-shaped molded product has a fine convex shape on one main surface and a large projected area of ​​the main surface. [Means for solving the problem]

[0007] The inventors have investigated a manufacturing method by injection molding that does not cause poor appearance or warping, even in plate-shaped molded products having fine convex shapes on one main surface and a large projected area of ​​the main surface.As a result, they have found that the above-mentioned problems can be solved by controlling the surface temperature of the fine convex shape-forming surface side of the mold and the opposing flat side within an appropriate temperature range during injection molding, and have thus completed the present invention.

[0008] That is, the present invention is as follows. [1] A method for producing a plate-shaped molded product, the plate-shaped molded product having a glass transition temperature (Tg) of 115 to 160°C and a melt viscosity of 270°C, 1000 sec -1 The adhesive layer is made of a single resin composition having a viscosity of 20 to 235 Pa sec at room temperature, and has no adhesive interface. One main surface (first main surface) of the plate-like molded product has a plurality of fine convex shapes, and the other main surface (second main surface) is a flat surface, a height a of the convex shape is 0.5 to 700 μm, and a ratio b / a of a pitch b of the convex shape to the height a of the convex shape is 0.1 to 2.0; The plate-shaped molded product has a projected area of ​​the first main surface of 225 cm 2 That's all. The method includes injection molding using a first mold on the side where the first main surface is formed and a second mold on the side where the second main surface is formed, wherein the maximum temperature Tmax of the first mold is set to (Tg+40)°C to (Tg+70)°C, and the temperature of the second mold is set to (Tmax-90)°C to (Tmax-65)°C. A method for producing a plate-shaped molded product, comprising: [2] The method for producing a plate-shaped molded product according to [1], wherein the tensile elongation at break of the methacrylic resin composition is 1.2% or more. [3] The method for producing a plate-like molded product according to [1] or [2], wherein the first mold is heated and then cooled so that the minimum temperature Tmin of the first mold is (Tg-75)°C to (Tg-45)°C. [4] The method for producing a plate-like molded product according to any one of [1] to [3], wherein when the first mold is heated and then cooled, the surface temperature of the first mold is increased at a rate of 1 to 10°C / sec and decreased at a rate of 0.5 to 10°C / sec. Effect of the Invention

[0009] According to the present invention, it is possible to produce a plate-shaped molded article having fine convex shapes on one main surface thereof, with reduced yellowing, poor appearance and warpage of the molded article. [Brief description of the drawings]

[0010] [Figure 1] 1 is a diagram showing an example of a plate-shaped molded product of this embodiment (corresponding to Examples 1 to 6), in which (A) shows a plan view (top view) when observed from above with the first main surface having a convex shape as the upper surface, and (B) shows a side view. [Diagram 2] FIG. 2 is a partial cross-sectional view showing an example of a convex shape (triangular pyramid shape) of the plate-like molded product of this embodiment. [Diagram 3] Fig. 3 is a diagram showing an example of a plate-shaped molded product of this embodiment (corresponding to Example 7) different from Fig. 1. (A) shows a plan view (top view) when observed from above with the first main surface having a convex shape as the upper surface, (B) shows a side view, and (C) shows a perspective view of the convex shape when observed obliquely from above. [Figure 4] FIG. 4 is a partial cross-sectional view showing an example of a convex shape (quadratic pyramid shape) of the plate-like molded product of this embodiment, which is different from that of FIG. [Diagram 5] FIG. 1 is a diagram showing the optical path when the plate-shaped molded products obtained in the examples and comparative examples are used as light direction conversion elements. [Figure 6] FIG. 1 is a layout diagram of equipment used to evaluate the characteristics of the plate-shaped molded products obtained in the examples and comparative examples when used as light direction conversion elements. [Figure 7] FIG. 7 is a plan view of the USAF Target 7 used in FIG. 6 as viewed from the X-axis direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Below, a form for implementing the present invention (hereinafter referred to as the "present embodiment") will be described in detail, but the present invention is not limited to the following description and can be implemented in various modified forms within the scope of its gist.

[0012] (Method of manufacturing plate-shaped molded products) The method for producing a plate-shaped molded product of this embodiment is a method for producing a plate-shaped molded product (hereinafter, simply referred to as a "molded product") containing a methacrylic resin composition described later, and includes injection molding using a first mold on the side that forms the first main surface (a main surface having a plurality of fine convex shapes) of the plate-shaped molded product and a second mold on the side that forms the second main surface (a main surface that is a flat surface) of the plate-shaped molded product, characterized in that the maximum temperature Tmax of the first mold is set to (Tg+40)°C to (Tg+70)°C (Tg is the glass transition temperature of the methacrylic resin composition) and the temperature of the second mold is set to (Tmax-90)°C to (Tmax-65)°C. The detailed conditions for injection molding in the method for producing a plate-shaped molded product according to this embodiment will be described below.

[0013] In this embodiment, the temperature setting from the nozzle tip to the center of the injection molding machine cylinder is set to (Tg+120)°C to (Tg+180)°C relative to the glass transition temperature Tg of the methacrylic resin composition used, so that the molten resin flows sufficiently and molding can be performed in a state in which deterioration due to thermal decomposition of the resin is suppressed. The temperature is preferably (Tg+125)°C to (Tg+170)°C, more preferably (Tg+130)°C to (Tg+165)°C, and even more preferably (Tg+130)°C to (Tg+160)°C. If the temperature during molding is within the above range, the flowability can be improved while suppressing the thermal decomposition of the resin, so that a plate-shaped molded product with good color tone and transfer rate of fine shapes tends to be obtained.

[0014] In this embodiment, the maximum temperature Tmax of the first mold when the resin is injected into the mold is controlled to a temperature range of (Tg+40)°C to (Tg+70)°C in order to improve the transferability (moldability) of fine convex shapes. It is preferably (Tg+45)°C to (Tg+65)°C, and more preferably (Tg+50)°C to (Tg+60)°C. When Tmax is (Tg+70)°C or less, the transferability and mold releasability tend to be good. On the other hand, when Tmax is (Tg+40)°C or more, the transferability tends to be good.

[0015] In this embodiment, when the maximum temperature of the first mold when the resin is injected into the mold is Tmax, the temperature of the second mold is set to (Tmax-90)°C to (Tmax-65)°C. It is preferably (Tmax-85)°C to (Tmax-70)°C, and particularly preferably (Tmax-80)°C to (Tmax-75)°C. When the temperature of the second mold is (Tmax-90)°C or higher, the amount of warping of the molded product tends to be small. On the other hand, when the temperature is (Tmax-65)°C or lower, the amount of warping of the molded product tends to be small, and deterioration of the flatness of the second main surface of the molded product due to the influence of thermal shrinkage of the resin and sticking to the mold is suppressed, so that a plate-shaped molded product with good appearance can be obtained.

[0016] In this embodiment, it is preferable to cool the first mold after heating. The minimum temperature Tmin of the first mold when cooled is preferably controlled in the temperature range of (Tg-75)°C to (Tg-45)°C, more preferably (Tg-70)°C to (Tg-50)°C, and even more preferably (Tg-65)°C to (Tg-55)°C. When Tmin is (Tg-75)°C or higher, it is possible to prevent the molding cycle from becoming extremely long and to suppress thermal deterioration of the resin in the cylinder. On the other hand, when it is (Tg-45)°C or lower, the amount of warping of the molded product tends to be small.

[0017] In this embodiment, the method of heating the mold is not particularly limited, and any method may be used. For example, a method of arranging a flow path for water or oil in the mold and adjusting the mold temperature to a temperature equal to or higher than the Tg of the methacrylic resin composition by a medium such as water or oil, a method of embedding a heater in the mold and heating the mold, a method of providing an electrically conductive layer that can be electrically conducted on the surface of the mold and heating the mold by generating heat by passing electricity through it, a method of heating from the outside or inside of the mold by an induction heating device, a method of heating from the outside of the mold by radiation of far infrared rays from a halogen lamp or a ceramic heater, etc. may be mentioned. In the present embodiment, the method for cooling the mold is not particularly limited and may be any method, for example, a method in which water or oil flow paths are provided in the mold and the mold is cooled by a medium such as water or oil.

[0018] In this embodiment, the rate of temperature rise of the surface temperature of the first mold during heating is preferably 1 to 10°C / sec, more preferably 1.5 to 10°C / sec, and even more preferably 2 to 10°C / sec. The faster the temperature rise rate, the more effective it is for shortening the cycle time, but it may be outside this range as long as there is no restriction on the cycle time and the deterioration of the resin due to heat retention in the cylinder is not a problem. In addition, the rate of temperature fall of the surface temperature of the first mold during cooling is preferably 0.5 to 10°C / sec, more preferably 1 to 10°C / sec, and even more preferably 2 to 10°C / sec. The faster the temperature fall rate, the more effective it is for shortening the cycle time, but as described later, it is more effective for improving the transferability to maintain the mold temperature at a high temperature. However, if the temperature fall rate is outside this range, it is not preferable because it tends to lead to a longer cycle time and worsening warpage of the molded product. In this embodiment, the temperature control can be appropriately set while observing the state of the molded product, such as raising and lowering the temperature at a constant rate, slowing down the rate of temperature increase and decrease, or holding at a predetermined temperature for a certain period of time. In order to improve the transfer of the convex shape, it is preferable to maintain the temperature at which the resin flows (preferably at or above the glass transition temperature) for a long time. Furthermore, if the holding time is short, birefringence will occur due to the formation of a skin layer, so from the viewpoint of suppressing this, it is preferable to slow down the rate of temperature decrease.

[0019] It is preferable to apply a release treatment to the surface of the mold. As the release treatment to the surface of the mold, an organic or inorganic release coating may be appropriately used. For example, organic coatings such as fluorine-based, silicone-based, and wax-based coatings, and inorganic coatings such as DLC-based, Cr-based, and Ti-based coatings can be used, and organic release coatings and inorganic release coatings can be used in combination. The release coating can be formed on the mold by a known wet method or dry method. However, when the depth of the fine convex shape of the mold is deep or the shape is complex, film formation by PVD (Physical Vapor Deposition), for example, film formation by vacuum deposition, sputtering, ion plating, etc., tends not to be able to form a coating deep into the fine convex shape. In terms of being able to apply a release coating deep into the fine convex shape and improving the releasability of the molded product, it is preferable to use a release agent that forms a release film by dissolving or dispersing a release component in a solvent, applying or spraying it on the mold, and drying or curing it.

[0020] (Plate-shaped molded product) The plate-shaped molded product of this embodiment is manufactured by the method for manufacturing a plate-shaped molded product of this embodiment, and has a glass transition temperature Tg of 115 to 160°C and a melt viscosity of 270°C and 1000 sec -1 the adhesive tape comprises a methacrylic resin composition having a viscosity of 20 to 235 Pa sec at 20° C., has no adhesive interface, and is composed of a single resin composition, one of the main surfaces (first main surface) has a plurality of fine convex shapes (hereinafter also referred to as "fine convex shape portion"), and the other main surface (second main surface) is flat, the height a of the convex shapes on the first main surface is 0.5 to 700 μm, the ratio b / a of the pitch b of the convex shapes to the height a of the convex shapes is 0.1 to 2.0, and the projected area of ​​the first main surface is 225 cm. 2 The present invention is characterized in that: The shape and other features of the plate-shaped molded product of this embodiment will be described in detail below.

[0021] The plate-shaped molded product of this embodiment does not have an adhesive interface and is composed of a single resin composition. By molding the fine convex portion and the plate-shaped portion (portion other than the fine convex portion) with a single resin composition by injection molding, and producing a molded product that does not have an adhesive interface between the fine convex portion and the plate-shaped portion, it is possible to obtain a plate-shaped molded product in which deterioration of appearance due to peeling at the adhesive interface is reduced.

[0022] In this embodiment, the fine convex shape formed on the first main surface is not particularly limited, and may be a polygonal pyramid such as a triangular pyramid, a square pyramid, or a pentagonal pyramid; a curved pyramid such as a circular cone, an elliptical cone, a semicone, a semi-elliptical cone, or an oblong cone (a cone having a cross section in a shape in which both ends of a pair of parallel straight lines are connected by a semicircle); a polygonal pyramid such as a truncated triangular pyramid, a truncated square pyramid, or a truncated pentagonal pyramid; a truncated circular cone, a truncated elliptical cone, a truncated semicone, a truncated semi-elliptical cone, or an oblong cone (a cone having a cross section in a shape in which both ends of a pair of parallel straight lines are connected by a semicircle); Examples of the shape include a curved frustum such as a truncated pyramid (a truncated pyramid having a cross section of a shape of a triangular prism, a quadrangular prism (a cube, a rectangular prism, etc.), a polygonal prism such as a pentagonal prism, a cylinder, an elliptical cylinder, a semi-circular cylinder, a semi-elliptical cylinder, an oblong cone (a cylinder having a cross section of a pair of parallel straight lines connected by a semicircle), and a dome shape (a structure having a hemisphere, a quarter sphere, an aspheric surface, etc., in which the cross-sectional area when cut in the axial direction gradually decreases toward the axially upward direction). In the case of a polygonal pyramid, a polygonal prism, etc., the corners may be rounded. In addition, the side surface of the convex shape may be flat or curved. These convex shapes may be of only one type or a combination of multiple types, but it is preferable that there is only one type. Fig. 2 is a partial cross-sectional view showing an example of a plate-shaped molded product of this embodiment in which the fine protrusions are triangular pyramids, and Fig. 4 is a partial cross-sectional view showing an example of a plate-shaped molded product of this embodiment in which the fine protrusions are quadrangular pyramids. The convex shapes may be arranged in a linear, curved, dot-like shape, etc. The convex shapes may be arranged over the entire surface of the first main surface, or may be arranged only in a partial area of ​​the first main surface. For example, Fig. 1(A) and Fig. 3(A) are plan views (top views) of an example of a plate-shaped molded product in which the convex shapes are arranged only in a partial area of ​​the first main surface, as viewed from the first main surface side.

[0023] In this embodiment, the ratio b / a of the pitch b to the height a of the fine convex shapes is 0.1 to 2.0, preferably 0.2 to 2.0, and more preferably 0.3 to 2.0. When b / a is in the above range, the molded product tends to be released cleanly from the mold while maintaining an extremely good mold transfer rate. b / a is the average value of the height and pitch of five or more convex shapes. Therefore, as long as b / a is within the above range, the height and pitch of each convex shape may be changed arbitrarily. The height a of the convex shape is 0.5 to 700 μm, preferably in the range of 50 to 650 μm, more preferably 200 to 600 μm, and further preferably 300 to 550 μm. When the height a of the convex shape is in the above range, warpage of the molded product according to the present invention tends to be effectively reduced. The pitch b of the convex shapes is preferably in the range of 100 to 500 μm, more preferably 150 to 450 μm, and even more preferably 180 to 400 μm. When the pitch b of the convex shapes is in the above range, warpage of the molded product tends to be effectively reduced. In this specification, the height of the convex shape means the highest value among the heights in the thickness direction of the molded product measured based on the flat portion of the first main surface parallel to the second main surface, and the height a is the average value of the heights of five or more convex shapes. For example, as shown in FIG. 2, when the convex shape is a pyramid, it means the height to the apex of the pyramid. When the first main surface does not have a flat portion parallel to the second main surface, the height of the convex shape may be the highest value among the heights in the thickness direction of the convex shape relative to the average thickness of the molded product. In addition, in this specification, the pitch of the convex shapes means the center-to-center distance between two adjacent convex shapes when the convex shapes are viewed in a plane (see Figures 2 and 4), and the pitch b is the average value of the pitches measured for five or more convex shapes. The height a and pitch b of the convex shape can be visually measured from an observation image obtained using an optical microscope, an electron microscope, a digital microscope, or the like, and specifically, can be measured by the method described in the examples below.

[0024] The size of the convex shape in plan view when observed from above with the first main surface as the upper surface is preferably 0.1 to 600 μm in diameter, more preferably 0.5 to 500 μm, and even more preferably 1 to 400 μm. In addition, when the above-mentioned planar shape of the convex shape is a line pattern, it means the length of the width in the direction perpendicular to the line direction, and in other cases, when the above-mentioned planar shape is a shape other than a circle, it means the diameter of the circumscribed circle. The diameter of the planar shape of the convex shape can be visually measured from an observation image obtained using an optical microscope, an electron microscope, a digital microscope, or the like. The size (height and diameter in plan view) of all the convex shapes may be the same or different.

[0025] The overall shape of the molded article of this embodiment is not particularly limited as long as it is a plate or approximately plate-like shape having a plurality of fine convex shapes on one main surface and the other main surface being flat. Examples of shapes (shapes seen in plan view) when observed from above with the first main surface having the fine convex shape as the upper surface include polygons such as triangles, squares, rectangles, parallelograms, trapezoids, and pentagons, circles, ellipses, semicircles, semi-ellipses, ovals (shapes formed by connecting both ends of a pair of parallel straight lines with a semicircle), and rings. In the case of polygons, the corners may be rounded. In addition, when the area of ​​the portion of the first main surface having a fine convex shape is taken as 100%, the area of ​​the flat portion of the second main surface on the reverse side may be 80% or more, and in consideration of mounting the molded article on various products, a part of the second main surface may have an uneven portion for connection to the product. The shape of the uneven portion for connection is not particularly limited, and for example, an uneven portion for connection having a size of 2 to 10 mm and a height of 2 to 10 mm may be provided near the outer periphery of the molded article for fixing to the product. Furthermore, from the viewpoint of demolding during molding, a frame for ejection by an ejector pin may be provided on the outer periphery of the molded product.

[0026] In this embodiment, the projected area of ​​the first main surface of the molded article is 225 cm 2 Above 225~2500cm 2may be 225 to 1000 cm 2 When the projected area of ​​the first main surface is within the above range, a molded article having a good appearance can be obtained without causing mold release defects. In this specification, the projected area of ​​the first main surface refers to the area of ​​the shape (planar shape) when the molded product is placed so that the first main surface is the upper surface and the first main surface is observed from above. For example, the molded product in FIG. 1(A) has an area of ​​552 cm 2 (=230mm×240mm), and the molded product in Fig. 3(A) is 702cm 2 (=260mm×270mm).

[0027] In this embodiment, the thickness of the molded product is preferably 1.5 mm or more and less than 6 mm, more preferably 2 mm or more and less than 5 mm, and even more preferably 2 mm or more and less than 4 mm, in terms of the thickness of the flat portion excluding the fine convex shapes. The thinner the thickness, the more difficult it is to control warpage, and the thicker the thickness, the more advantageous it is for controlling warpage, but it takes time to cool during molding, a temperature difference occurs between the surface and the inside, the center is recessed, the flatness of the flat portion is impaired, and there is a risk of adversely affecting the optical properties of the molded product. The size of each main surface of the molded article is not particularly limited and may be set according to the purpose.

[0028] The packing degree of the plate-shaped molded product of this embodiment is preferably 0.92 or more, more preferably 0.95 or more, and even more preferably 0.99 or more. When the packing degree is 0.92 or more, it can be said that the molded product has a well-formed convex shape. The filling degree is a value calculated from the height a of the convex shape and the depth of the concave shape in the first mold for forming the convex shape by the following formula, and is the average value at four points. Specifically, it can be measured by the method described in the examples below. (Filling degree) = (height a of the convex shape of the molded product) / (depth a of the concave shape of the mold)

[0029] In the plate-shaped molded product of this embodiment, when the second main surface has no unevenness as shown in Fig. 1, the amount of warping is preferably 0.4 mm or less, more preferably 0.35 mm or less, and further preferably 0.3 mm or less. If the amount of warping is 0.4 mm or less, the molded product can be said to have good dimensional accuracy. In addition, the square root of the area of ​​the region where the convex shape is formed is calculated when the surface on which the convex shape is formed is viewed in plan view with the surface on which the convex shape is formed as the upper surface (for example, in FIG. 1, the shaping surface area is 210 mm square, so the square root is 210 mm), and if the warpage amount for the obtained value is 0.50% or less, it can be determined that the dimensional accuracy of the molded product is within a preferable range. It is more preferably 0.44% or less, and even more preferably 0.38% or less. The amount of warping is the value at the location with the largest gap when the molded product is placed on a metal platen with the first main surface facing up, the outer periphery of the molded product is equally divided into four points, and the gap between the molded product and the platen is measured at the four points (see, for example, 15a to 15d in Figure 1). Specifically, the amount of warping can be measured by the method described in the examples below.

[0030] The plate-shaped molded product of the present embodiment has a birefringence value, expressed as an in-plane retardation, of preferably 100 nm or less, more preferably 50 nm or less, and further preferably 20 nm or less. When the in-plane retardation is within the above range, the optical properties are less likely to be adversely affected. The in-plane retardation can be measured by the method described in the Examples below.

[0031] In the plate-shaped molded product of this embodiment, the amount of methyl methacrylate (MMA) contained in the plate-shaped molded product is preferably 1600 to 6000 mass ppm, more preferably 1800 to 5000 mass ppm, and further preferably 2000 to 4000 mass ppm. When the amount of MMA in the plate-shaped molded product is 6000 mass ppm or less, a molded product with low yellowness and good appearance tends to be obtained. On the other hand, when the amount of MMA in the plate-shaped molded product is 1600 mass ppm or more, a molded product with good filling degree of fine convex shapes and low yellowness tends to be obtained. The amount of MMA contained in the plate-shaped molded product can be measured by the method described in the Examples below.

[0032] The plate-shaped molded product of the present embodiment preferably has a yellowness index (YI) of 3.0 to 10.0, more preferably 3.0 to 9.0, and even more preferably 3.0 to 8.0. When the yellowness index (YI) is within the above range, the yellowness degree tends to be low and the appearance tends to be good. The yellowness index (YI) can be measured by the method described in the Examples section below.

[0033] (Methacrylic resin composition) The methacrylic resin composition used in the method for producing a plate-shaped molded product of the present embodiment is characterized by containing a methacrylic resin, and may optionally contain additives in addition to the methacrylic resin. Also, the methacrylic resin may contain other thermoplastic resins, rubbery polymers, and the like, other than the methacrylic resin.

[0034] -Methacrylic resin- The characteristics of the methacrylic resin used in this embodiment will be described below.

[0035] The methacrylic resin used in the present embodiment is not particularly limited, and examples thereof include resins mainly composed of structural units derived from methyl methacrylate, such as a homopolymer of methyl methacrylate, or a copolymer of methyl methacrylate with one or more copolymerizable monomers such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, butyl acrylate, acrylonitrile, acrylic acid, methacrylic acid, vinylpyridine, vinylmorpholine, vinylpyridone tetrahydrofurfuryl acrylate, N,N-dimethylaminoethyl acrylate, N,N-dimethylacrylamide, 2-hydroxyacrylate, 2-(hydroxymethyl)ethyl acrylate, ethylene glycol monoacrylate, glycerin monoacrylate, maleic anhydride, N-cyclohexylmaleimide, N-phenylmaleimide, styrene, or α-methylstyrene. Other examples include heat-resistant methacrylic resins having a structural unit derived from methyl methacrylate and a lactone ring or glutarimide in the main chain, methyl methacrylate and low-hygroscopic methacrylic resins, etc. These may be used alone or in a blend of two or more. The phrase "mainly composed of structural units derived from methyl methacrylate" means that structural units derived from methyl methacrylate account for 50 mass % or more of the structural units in the methacrylic resin.

[0036] The methacrylic resin in this embodiment is preferably a methacrylic resin having a structural unit with a ring structure, from the viewpoints of transparency and heat resistance. The structural unit having a ring structure preferably contains at least one structural unit selected from the group consisting of a structural unit derived from an N-substituted maleimide monomer, a glutarimide structural unit, an aromatic vinyl structural unit, an alicyclic vinyl structural unit, and a lactone ring structural unit. In addition, it is particularly preferable that the structural unit having a ring structure contains a structural unit derived from an N-substituted maleimide monomer, since optical properties such as intrinsic birefringence and photoelastic coefficient can be easily controlled to a high degree without blending with other thermoplastic resins.

[0037] --Structural units derived from N-substituted maleimide monomers-- Next, the structural unit derived from the N-substituted maleimide monomer will be described. The structural unit derived from the N-substituted maleimide monomer may be at least one structural unit selected from the group consisting of a structural unit represented by the following formula (1) and a structural unit represented by the following formula (2), and is preferably formed from both of the structural units represented by the following formula (1) and the following formula (2).

[0038] [ka] In formula (1), R 1 represents an arylalkyl group having 7 to 14 carbon atoms or an aryl group having 6 to 14 carbon atoms; R 2 and R 3 each independently represents a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms. Also, R 2 or R 3 When is an aryl group, R 2 or R 3 may contain a halogen atom as a substituent. Also, R 1 may be substituted with a substituent such as a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, or a benzyl group. [ka] In formula (2), R 4 represents a hydrogen atom, a cycloalkyl group having 3 to 12 carbon atoms, or an alkyl group having 1 to 12 carbon atoms; R 5 and R 6 each independently represents a hydrogen atom, an oxygen atom, a sulfur atom, an alkyl group having 1 to 12 carbon atoms, or an aryl group having 6 to 14 carbon atoms.

[0039] In the above formula (1), examples of the arylalkyl group having 7 to 14 carbon atoms include, but are not limited to, a benzyl group, a phenylethyl group, a phenylpropyl group, a naphthylmethyl group, a naphthylethyl group, and a naphthylpropyl group.

[0040] In the above formulas (1) and (2), the aryl group having 6 to 14 carbon atoms is not limited, but examples thereof include a phenyl group, a tolyl group, a xylyl group, a naphthyl group, a biphenyl group, an anthracenyl group, and a phenanthryl group.

[0041] In the above formula (1) and formula (2), the alkyl group having 1 to 12 carbon atoms may be linear or branched, and is not particularly limited, but examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, a sec-butyl group, an isobutyl group, a tert-butyl group, a 2-methylbutyl group, an n-pentyl group, a 2-pentyl group, a 3-pentyl group, a 2,2-dimethylpropyl group, an n-hexyl group, a heptyl group, an n-octyl group, a 1,1,3,3-tetramethylbutyl group, a 2-ethylhexyl group, a nonyl group, a decyl group, an undecyl group, and a dodecyl group.

[0042] In the above formula (1), examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom.

[0043] In the above formula (1), the alkoxy group having 1 to 6 carbon atoms is not limited, but examples thereof include a methoxy group, an ethoxy group, an n-butoxy group, and a methoxyethoxy group.

[0044] In the above formula (1), examples of the cycloalkyl group having 3 to 12 carbon atoms include, but are not limited to, a cyclopropyl group, a cyclopropylmethyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cyclohexylmethyl group, a trimethylcyclohexyl group, a thujyl group, a norbornyl group, a bornyl group, a norcaryl group, a caryl group, a menthyl group, a norpinyl group, a pinyl group, a 1-adamantyl group, and a 2-adamantyl group.

[0045] Specific examples are given below. Examples of monomers (N-arylmaleimides, N-aromatic substituted maleimides, etc.) that form the structural unit represented by formula (1) include N-phenylmaleimide, N-benzylmaleimide, N-(2-chlorophenyl)maleimide, N-(4-chlorophenyl)maleimide, N-(4-bromophenyl)maleimide, N-(2-methylphenyl)maleimide, N-(2,6-dimethylphenyl)maleimide, N-(2-ethylphenyl)maleimide, N-(2-methoxyphenyl)maleimide, N-(2-nitrophenyl)maleimide, N-phenyl ... N-(2,4,6-trimethylphenyl)maleimide, N-(4-benzylphenyl)maleimide, N-(2,4,6-tribromophenyl)maleimide, N-naphthylmaleimide, N-anthracenylmaleimide, 3-methyl-1-phenyl-1H-pyrrole-2,5-dione, 3,4-dimethyl-1-phenyl-1H-pyrrole-2,5-dione, 1,3-diphenyl-1H-pyrrole-2,5-dione, 1,3,4-triphenyl-1H-pyrrole-2,5-dione, and the like. Among these monomers, N-phenylmaleimide and N-benzylmaleimide are preferred because of their excellent heat resistance and optical properties such as birefringence. These monomers may be used alone or in combination of two or more kinds.

[0046] Examples of the monomer that forms the structural unit represented by formula (2) include N-methylmaleimide, N-ethylmaleimide, Nn-propylmaleimide, N-isopropylmaleimide, Nn-butylmaleimide, N-isobutylmaleimide, Ns-butylmaleimide, Nt-butylmaleimide, Nn-pentylmaleimide, Nn-hexylmaleimide, Nn-heptylmaleimide, Nn-octylmaleimide, and N- Examples of the maleimide include laurylmaleimide, N-cyclopentylmaleimide, N-cyclohexylmaleimide, 1-cyclohexyl-3-methyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3,4-dimethyl-1H-pyrrole-2,5-dione, 1-cyclohexyl-3-phenyl-1H-pyrrole-2,5-dione, and 1-cyclohexyl-3,4-diphenyl-1H-pyrrole-2,5-dione. Among these monomers, N-methylmaleimide, N-ethylmaleimide, N-isopropylmaleimide, and N-cyclohexylmaleimide are preferred because they provide excellent weather resistance to the methacrylic resin, and N-cyclohexylmaleimide is particularly preferred because it has excellent low moisture absorption, which is a requirement for optical materials in recent years. These monomers can be used alone or in combination of two or more.

[0047] In the methacrylic resin in the methacrylic resin composition, it is particularly preferable to use a structural unit represented by formula (1) in combination with a structural unit represented by formula (2) in order to develop highly controlled birefringence characteristics. The molar ratio (X1 / X2) of the content (X1) of the structural unit represented by formula (1) to the content (X2) of the structural unit represented by formula (2) is preferably more than 0 and not more than 15, more preferably more than 0 and not more than 10. When the molar ratio (X1 / X2) is within this range, the plate-shaped molded product of the present embodiment maintains its transparency, is not yellowed, and exhibits good heat resistance and good photoelastic properties without impairing environmental resistance.

[0048] The content of the structural unit derived from the N-substituted maleimide monomer is preferably in the range of 5 to 40% by mass, more preferably in the range of 5 to 35% by mass, based on 100% by mass of the methacrylic resin. When the content of the structural unit derived from the N-substituted maleimide monomer is within this range, the methacrylic resin can obtain a more sufficient heat resistance improving effect, and can obtain more preferable improving effects on weather resistance, low water absorption, and optical properties. In addition, keeping the content of the structural unit derived from the N-substituted maleimide monomer to 40% by mass or less is effective in preventing a decrease in the physical properties of the methacrylic resin due to a decrease in the reactivity of the monomer component during the polymerization reaction and an increase in the amount of unreacted remaining monomer. In addition, by appropriately adjusting the content of the structural units derived from the N-substituted maleimide monomer within this range, it is possible to reduce birefringence caused by orientation during molding or residual stress, and obtain a plate-shaped molded product with an average absolute value of in-plane retardation of 100 nm or less. The optimal content of the structural units derived from the N-substituted maleimide monomer varies depending on the type of N-substituted maleimide, but for example, when methyl methacrylate is used as the methacrylic acid ester monomer and N-phenylmaleimide and N-cyclohexylmaleimide are used as the N-substituted maleimide monomer, it is preferable to adjust the content within the range of 79 to 83 mass% of the structural units derived from methyl methacrylate, 6 to 8 mass% of the structural units derived from N-phenylmaleimide, and 11 to 13 mass% of the structural units derived from N-cyclohexylmaleimide.

[0049] The methacrylic resin having a structural unit derived from an N-substituted maleimide monomer may contain a structural unit derived from another monomer copolymerizable with the methacrylic acid ester monomer and the N-substituted maleimide monomer, as long as the object of the present invention is not impaired. For example, the other copolymerizable monomers include aromatic vinyls; unsaturated nitriles; acrylic esters having a cyclohexyl group, a benzyl group, or an alkyl group having 1 to 18 carbon atoms; glycidyl compounds; and unsaturated carboxylic acids. Examples of the aromatic vinyl include styrene, α-methylstyrene, and divinylbenzene. Examples of the unsaturated nitrile include acrylonitrile, methacrylonitrile, and ethacrylonitrile. Examples of the acrylic ester include methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, and butyl acrylate. The glycidyl compound includes glycidyl (meth)acrylate and the like. The unsaturated carboxylic acids include acrylic acid, methacrylic acid, itaconic acid, maleic acid, fumaric acid, and half-esters or anhydrides thereof. The structural unit derived from the other copolymerizable monomer may be of only one type, or may be of two or more types.

[0050] The content of structural units derived from these other copolymerizable monomers is preferably 0 to 10 mass%, more preferably 0 to 9 mass%, and even more preferably 0 to 8 mass%, based on 100 mass% of the methacrylic resin. If the content of the structural units derived from other monomers is within this range, the molding processability and mechanical properties of the resin can be improved without impairing the inherent effect of introducing a ring structure, which is preferable.

[0051] The content of the structural unit derived from the N-substituted maleimide monomer and the content of the structural unit derived from other copolymerizable monomers are as follows: 1 H-NMR measurement and 13 It can be determined by C-NMR measurement. 1 H-NMR measurement and 13 C-NMR measurement can be carried out, for example, using CDCl3 or DMSO-d6 as a measurement solvent at a measurement temperature of 40°C.

[0052] --Glutarimide structural unit-- Examples of methacrylic resins having glutarimide structural units include methacrylic resins having glutarimide structural units described in JP-A-2006-249202, JP-A-2007-009182, JP-A-2007-009191, JP-A-2011-186482, and Republished Patent Publication No. 2012 / 114718, and can be formed by the methods described in these publications. The glutarimide structural unit constituting the methacrylic resin may be formed after polymerization of the resin. Specifically, the glutarimide structural unit may be represented by the following general formula (3).

[0053] [ka] In the above general formula (3), preferably R 7 and R 8 are each independently a hydrogen atom or a methyl group, R 9 is any one of a hydrogen atom, a methyl group, a butyl group, and a cyclohexyl group, and more preferably, R 7 is a methyl group, and R 8 is a hydrogen atom, and R 9 is a methyl group. The glutarimide-based structural unit may include only one type, or may include a plurality of types.

[0054] In the methacrylic resin having a glutarimide structural unit, the content of the glutarimide structural unit is preferably in the range of 3 to 70 mass %, more preferably in the range of 3 to 60 mass %, based on 100 mass % of the methacrylic resin. It is preferable that the content of the glutarimide structural unit is within the above range, since a resin having good moldability, heat resistance, and optical properties can be obtained. In addition, by appropriately adjusting the content of the glutarimide structural unit within this range, it is possible to reduce the birefringence caused by the orientation during molding or residual stress, and obtain a plate-shaped molded product having an average absolute value of the in-plane retardation of 100 nm or less.7 ~R 9 The optimum content of glutarimide structural units varies depending on the type of the substituent of R. 7 and R 8 is a hydrogen atom, R 9 When the is a methyl group, if the content of the glutarimide structural unit is in the range of 3 to 10 mass %, the birefringence caused by the orientation or residual stress during molding can be reduced, and a plate-shaped molded product having an average absolute value of the in-plane retardation of 100 nm or less can be obtained. The content of glutarimide structural units in the methacrylic resin can be determined by the method described in the aforementioned patent document.

[0055] The methacrylic resin having a glutarimide structural unit may further contain an aromatic vinyl monomer unit, if necessary. The aromatic vinyl monomer is not particularly limited, but examples thereof include styrene and α-methylstyrene, with styrene being preferred.

[0056] The content of aromatic vinyl units in the methacrylic resin having glutarimide structural units is not particularly limited, but is preferably 0 to 20% by mass, with the methacrylic resin having glutarimide structural units being 100% by mass. When the content of the aromatic vinyl unit is within the above range, it is possible to achieve both heat resistance and excellent photoelasticity, which is preferable. For example, when a resin is obtained by glutarimidating a methyl methacrylate-styrene copolymer obtained by copolymerizing methyl methacrylate as the methacrylic acid ester monomer and styrene as the aromatic vinyl monomer, by adjusting the ranges of 65 to 90 mass% of structural units derived from methyl methacrylate, 5 to 15 mass% of structural units derived from styrene, and 5 to 20 mass% of glutarimide-based structural units, it is possible to reduce birefringence caused by orientation and residual stress during molding and to obtain a plate-shaped molded product with an average absolute value of in-plane retardation of 100 nm or less.

[0057] --Aromatic vinyl structural unit-- The aromatic vinyl structural unit is not particularly limited, but examples thereof include structural units derived from styrene and α-methylstyrene, with a structural unit derived from styrene being preferred.

[0058] --Alicyclic vinyl structural unit-- The alicyclic vinyl structural unit can be formed by the methods described in, for example, JP-A Nos. 2006-291184, 2006-291184, 2014-77043, and 2014-77044.

[0059] --Lactone ring structural unit-- Methacrylic resins having a lactone ring structural unit can be formed by the methods described in, for example, JP-A Nos. 2001-151814, 2004-168882, 2005-146084, 2006-96960, 2006-171464, 2007-63541, 2007-297620, and 2010-180305.

[0060] The lactone ring structural unit constituting the methacrylic resin may be formed after polymerization of the resin. The lactone ring structural unit in this embodiment is preferably a six-membered ring because this provides excellent stability of the ring structure. As the 6-membered lactone ring structural unit, for example, a structure represented by the following general formula (4) is particularly preferred.

[0061] [ka]

[0062] In the above general formula (4), R 10 , R 11 and R 12 are each independently a hydrogen atom or an organic residue having 1 to 20 carbon atoms. Examples of the organic residue include saturated aliphatic hydrocarbon groups (alkyl groups, etc.) having 1 to 20 carbon atoms, such as a methyl group, an ethyl group, a propyl group, etc.; unsaturated aliphatic hydrocarbon groups (alkenyl groups, etc.) having 2 to 20 carbon atoms, such as an ethenyl group, a propenyl group, etc.; aromatic hydrocarbon groups (aryl groups, etc.) having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, etc.; and groups in which one or more hydrogen atoms in these saturated aliphatic hydrocarbon groups, unsaturated aliphatic hydrocarbon groups, and aromatic hydrocarbon groups have been substituted with at least one group selected from the group consisting of a hydroxy group, a carboxyl group, an ether group, and an ester group.

[0063] The lactone ring structural unit can be formed, for example, by copolymerizing an acrylic acid monomer having a hydroxy group with a methacrylic acid ester monomer such as methyl methacrylate to introduce a hydroxy group and an ester group or a carboxyl group into the molecular chain, and then causing dealcoholization (esterification) or dehydration condensation (hereinafter also referred to as a "cyclization condensation reaction") between the hydroxy group and the ester group or the carboxyl group.

[0064] Examples of the acrylic acid monomer having a hydroxy group used in the polymerization include 2-(hydroxymethyl)acrylic acid, 2-(hydroxyethyl)acrylic acid, 2-(hydroxymethyl)alkyl acrylates (e.g., methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, isopropyl 2-(hydroxymethyl)acrylate, n-butyl 2-(hydroxymethyl)acrylate, t-butyl 2-(hydroxymethyl)acrylate), and 2-(hydroxyethyl)alkyl acrylates. Preferred are 2-(hydroxymethyl)acrylic acid and 2-(hydroxymethyl)alkyl acrylates, which are monomers having a hydroxyalkyl moiety, and particularly preferred are methyl 2-(hydroxymethyl)acrylate and ethyl 2-(hydroxymethyl)acrylate.

[0065] The content of the lactone ring structural unit in the methacrylic resin having the lactone ring structural unit is preferably from 5 to 40 mass %, and more preferably from 5 to 35 mass %, relative to 100 mass % of the methacrylic resin. When the content of the lactone ring structural unit is within this range, the effects of introducing a ring structure, such as improved solvent resistance and improved surface hardness, can be achieved while maintaining moldability. In addition, by appropriately adjusting the content of the lactone ring structural unit within this range, it is possible to reduce birefringence caused by orientation and residual stress during molding and to obtain a plate-shaped molded product having an average absolute value of in-plane retardation of 100 nm or less. The content of the lactone ring structure in the methacrylic resin can be determined by the method described in the aforementioned patent document.

[0066] The methacrylic resin having a lactone ring structural unit may have a structural unit derived from another monomer copolymerizable with the above-mentioned methacrylic acid ester monomer and acrylic acid monomer having a hydroxy group. Examples of such other copolymerizable monomers include monomers having a polymerizable double bond, such as styrene, vinyl toluene, α-methyl styrene, α-hydroxymethyl styrene, α-hydroxyethyl styrene, acrylonitrile, methacrylonitrile, methallyl alcohol, ethylene, propylene, 4-methyl-1-pentene, vinyl acetate, 2-hydroxymethyl-1-butene, methyl vinyl ketone, N-vinylpyrrolidone, and N-vinyl carbazole. The copolymer may contain only one type of these other monomers (structural units), or may contain two or more types.

[0067] The content of structural units derived from these other copolymerizable monomers is preferably 0 to 20 mass% relative to 100 mass% of the methacrylic resin, and from the viewpoint of weather resistance, it is more preferably less than 10 mass%, and even more preferably less than 7 mass%. The methacrylic resin in the present embodiment may have only one type of structural unit derived from the other copolymerizable monomer, or may have two or more types.

[0068] -Methacrylic resin manufacturing method- The method for producing the methacrylic resin of this embodiment will be described below.

[0069] In the production method of this embodiment, a batch system, a semi-batch system, or a continuous system can be used as the polymerization system. Here, the batch system is a process in which the reaction is started and proceeded after the entire amount of raw materials is charged into a reactor, and the product is recovered after the reaction is completed. The semi-batch system is a process in which either the raw materials are charged or the product is recovered simultaneously during the reaction, and the continuous system is a process in which both the raw materials are charged and the product is recovered simultaneously during the reaction. As the production method of the methacrylic resin in this embodiment, a semi-batch system in which a part of the raw materials is charged after the reaction is started is preferable from the viewpoint of precisely controlling the copolymer composition. The continuous method is not preferred as a production method in this embodiment for the following reasons. When the polymerization reaction is carried out in one complete mixing reactor, the continuous method has the advantage that the difference in monomer composition between the fractions having different molecular weights in the methacrylic resin can be reduced, but since a large amount of unreacted monomer remains after polymerization, it tends to have an adverse effect on the color tone. On the other hand, when a plug flow reactor is used, the amount of unreacted monomer can be reduced, but the difference in monomer composition between the fractions having different molecular weights in the methacrylic resin tends to be large. Even when multiple complete mixing reactors or a complete mixing reactor and a plug flow reactor are combined in series, the amount of unreacted monomer can be reduced, but the difference in monomer composition between the fractions tends to be large.

[0070] The polymerization solvent is not particularly limited, and examples of the polymerization solvent that can be used include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and isopropylbenzene; esters such as methyl isobutyrate; ketones such as methyl isobutyl ketone, butyl cellosolve, methyl ethyl ketone, and cyclohexanone; and polar solvents such as dimethylformamide and 2-methylpyrrolidone. Furthermore, alcohols such as methanol, ethanol, and isopropanol may be used in combination as a polymerization solvent within a range that does not inhibit dissolution of the polymerization product during polymerization. The amount of the solvent during polymerization is not particularly limited as long as the polymerization proceeds and the amount can be easily removed without causing precipitation of the copolymer or monomers used during production. For example, when the total amount of the monomers to be blended is 100 parts by mass, the amount of the solvent is preferably 10 to 200 parts by mass, more preferably 25 to 200 parts by mass, even more preferably 50 to 200 parts by mass, and even more preferably 50 to 150 parts by mass.

[0071] As the polymerization initiator, any initiator generally used in radical polymerization can be used. Examples of the polymerization initiator include organic peroxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, di-t-butyl peroxide, lauroyl peroxide, benzoyl peroxide, t-butylperoxyisopropyl carbonate, t-amylperoxy-2-ethylhexanoate, t-amylperoxyisononanoate, and 1,1-di(t-butylperoxy)cyclohexane; and azo compounds such as 2,2'-azobis(isobutyronitrile), 1,1'-azobis(cyclohexanecarbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and dimethyl-2,2'-azobisisobutyrate. These may be used alone or in combination of two or more. These polymerization initiators may be added at any stage as long as the polymerization reaction is in progress. The amount of the polymerization initiator added may be 0.01 to 1 part by mass, and preferably 0.05 to 0.5 part by mass, relative to 100 parts by mass of the total amount of the monomers used in the polymerization.

[0072] As the chain transfer agent, any chain transfer agent used in general radical polymerization can be used, and examples thereof include mercaptan compounds such as n-butyl mercaptan, n-octyl mercaptan, n-decyl mercaptan, n-dodecyl mercaptan, 2-ethylhexyl thioglycolate, etc.; halogen compounds such as carbon tetrachloride, methylene chloride, bromoform, etc.; unsaturated hydrocarbon compounds such as α-methylstyrene dimer, α-terpinene, dipentene, terpinolene, etc.; and the like. These may be used alone or in combination of two or more. These chain transfer agents may be added at any stage as long as the polymerization reaction is in progress, and there are no particular limitations on the addition stage. The amount of the chain transfer agent added may be 0.01 to 1 part by mass, and preferably 0.05 to 0.5 part by mass, based on 100 parts by mass of the total amount of monomers used in the polymerization.

[0073] The method for recovering the polymer from the polymerization liquid obtained by solution polymerization is not particularly limited, and examples thereof include a method in which the polymerization liquid is added to an excess of a poor solvent such as a hydrocarbon solvent or an alcohol solvent in which the polymerization product obtained by polymerization is not dissolved, and then the mixture is treated with a homogenizer (emulsion dispersion), and unreacted monomers are separated from the polymerization liquid by pretreatment such as liquid-liquid extraction or solid-liquid extraction; or a method in which the polymerization solvent and unreacted monomers are separated via a process called a devolatilization process, and the polymerization product is recovered. The devolatilization step here refers to a step of removing volatile matters such as the polymerization solvent, residual monomers, and reaction by-products under heating and reduced pressure conditions.

[0074] Examples of equipment used in the devolatilization step include a devolatilizer consisting of a tubular heat exchanger and a devolatilization tank; thin-film evaporators such as Wiblen and Exeva manufactured by Kobelco Environmental Solutions Co., Ltd., and Contra and tilted blade Contra manufactured by Hitachi, Ltd.; and a vented extruder having a residence time and surface area sufficient to exhibit devolatilization performance. A devolatilization step using a devolatilization apparatus that combines two or more of these devices can also be used.

[0075] From the viewpoint of improving the color tone, it is preferable to use a volatilization apparatus that is mainly composed of a heat exchanger and a reduced pressure vessel and does not have a rotating part in its structure. Specifically, a volatilizing apparatus can be used which is composed of a volatilizing tank having a reduced pressure vessel with a heat exchanger disposed on the upper portion thereof and a size allowing volatilization, to which a reduced pressure unit is attached, and a discharge device such as a gear pump for discharging the polymer after volatilization. In the above-mentioned volatilizing apparatus, the polymerization solution is preheated by being fed to a heated heat exchanger, such as a multi-tube heat exchanger, a plate fin heat exchanger, or a flat plate heat exchanger having a flat plate flow path and a heater, which is disposed in the upper part of the reduced pressure vessel, and then fed to a volatilizing tank which is heated and under reduced pressure, to separate and remove the polymerization solvent, the unreacted raw material mixture, the polymerization by-products, and the copolymer. The use of a volatilizing apparatus having no rotating part as described above is preferable because it allows the production of a methacrylic resin having a good color tone.

[0076] The treatment temperature in the devolatilizer is preferably 150 to 350° C., more preferably 170 to 300° C., and further preferably 200 to 280° C. By setting the temperature to be equal to or higher than the lower limit, the amount of remaining volatile matter can be suppressed, and by setting the temperature to be equal to or lower than the upper limit, coloration and decomposition of the obtained acrylic resin can be suppressed.

[0077] -Additives- The methacrylic resin composition according to the present embodiment may contain various additives within the range that does not significantly impair the effects of the present invention. The additives are not particularly limited, and examples thereof include antioxidants, light stabilizers such as hindered amine light stabilizers, ultraviolet absorbers, release agents, thermoplastic resins other than methacrylic resins, softeners / plasticizers such as paraffinic process oil, naphthenic process oil, aromatic process oil, paraffin, organic polysiloxane, and mineral oil, flame retardants, antistatic agents, inorganic fillers such as organic fibers and pigments such as iron oxide, reinforcing agents such as glass fibers, carbon fibers, and metal whiskers, colorants, and organic phosphorus compounds such as phosphites, phosphonites, and phosphate esters, and mixtures thereof.

[0078] --Antioxidants-- The methacrylic resin composition according to the present embodiment preferably contains an antioxidant that suppresses deterioration and coloration during molding or use. The antioxidant is not limited to the following, but examples thereof include hindered phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants. In order to highly control the distortion and warping of the surface of the molded product while increasing the transferability of the fine convex shaped portion of the first mold, it is essential that the resin is kept at a high temperature in the mold cavity and a moderate cooling time is provided. When subjected to a long-term thermal history, it is necessary to increase the amount of heat stabilizer added to obtain the desired thermal stability, but from the viewpoint of suppressing bleed-out of the heat stabilizer and preventing it from sticking to the mold, it is preferable to use multiple types of heat stabilizers in combination, for example, it is preferable to use at least one selected from a phosphorus-based antioxidant and a sulfur-based antioxidant in combination with a hindered phenol-based antioxidant. These antioxidants may be used alone or in combination of two or more.

[0079] Examples of the hindered phenol-based antioxidant include, but are not limited to, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], thiodiethylene bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,3',3'',5,5',5''-hexa-tert-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, 4,6-bis(octylthiomethyl)-o-cresol, 4,6-bis(dodecylthiomethyl)-o-cresol, ethylene bis(oxyethylene)bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate], hexamethylene bis[ 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 1,3,5-tris[(4-tert-butyl-3-hydroxy-2,6-xylin)methyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 2 ,6-di-tert-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamine)phenol, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, and the like. In particular, pentaerythritol terakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, and 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate are preferred.

[0080] In addition, the hindered phenol-based antioxidant used as the antioxidant may be a commercially available phenol-based antioxidant. Examples of such commercially available phenol-based antioxidants include, but are not limited to, Irganox 1010 (Irganox 1010: pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], manufactured by BASF), Irganox 1076 (Irganox 1076: Octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, BASF), Irganox 1330 (Irganox 1330: 3,3',3'',5,5',5''-hexa-t-butyl-a,a',a''-(mesitylene-2,4,6-triyl)tri-p-cresol, BASF), Irganox 3114 (Irganox 3114: 1,3,5-tris(3,5-di-t-butyl-4-hydroxybenzyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, B ASF), Irganox 3125 (BASF), Adeka STAB AO-60 (pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], ADEKA), Adeka STAB AO-80 (3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1-dimethylethyl}-2,4,8,10-tetraoxaspiro[5.5]undecane, ADEKA), Sumilizer BHT (Sumilizer BHT, manufactured by Sumitomo Chemical), Cyanox 1790 (manufactured by Cytec), Sumilizer GA-80 (manufactured by Sumitomo Chemical), Sumilizer GS (Sumilizer GS: 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, manufactured by Sumitomo Chemical), Sumilizer GM (Sumilizer GM: 2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl acrylate, manufactured by Sumitomo Chemical), and Vitamin E (manufactured by Eisai). Among these commercially available phenolic antioxidants, Irganox 1010, Adeka STAB AO-60, Adeka STAB AO-80, Irganox 1076, Sumilizer GS, and the like are preferred from the viewpoint of the effect of imparting thermal stability to the resin. These may be used alone or in combination of two or more.

[0081] In addition, examples of the phosphorus-based antioxidant as the antioxidant include, but are not limited to, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, tetrakis(2,4-di-t-butylphenyl)(1,1-biphenyl)-4,4'-diyl bisphosphonite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, bis(2,6-di-t-butyl-4-methyl phenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetrakis(2,4-t-butylphenyl)(1,1-biphenyl)-4,4'-diylbisphosphonite, di-t-butyl-m-cresyl-phosphonite, 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, and the like. Furthermore, commercially available phosphorus-based antioxidants may be used as the phosphorus-based antioxidant. Examples of commercially available phosphorus-based antioxidants include, but are not limited to, Irgafos 168 (Irgafos 168: tris(2,4-di-t-butylphenyl)phosphite, manufactured by BASF), Irgafos 12 (Irgafos 12: tris[2-[[2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxaphosphen-6-yl]oxy]ethyl]amine, manufactured by BASF), Irgafos 38 (Irgafos 38: bis(2,4-bis(1,1-dimethylethyl)-6-methylphenyl)ethyl ester phosphorous acid, manufactured by BASF), ADK STAB 329K (ADK STAB-229K, manufactured by ADEKA), ADK STAB PEP-36 (ADK STAB PEP-36, manufactured by ADEKA), ADK STAB PEP-36A, ADK STAB PEP-8, ADK STAB HP-10, ADK STAB HP-10, ADK STAB 2112, manufactured by ADEKA, ADK STAB 1178, manufactured by ADEKA, ADK STAB 1500, manufactured by ADEKA, Sandstab P-EPQ, manufactured by Clariant, Weston 618, manufactured by GE, Weston 619G, manufactured by GE, Ultranox 626, manufactured by GE, Sumilizer GP GP: 4-[3-[(2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin)-6-yloxy]propyl]-2-methyl-6-tert-butylphenol, manufactured by Sumitomo Chemical Co., Ltd.), HCA (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, manufactured by Sanko Co., Ltd.), and the like. Among these commercially available phosphorus-based antioxidants, from the viewpoint of the effect of imparting thermal stability to the resin and the effect of using them in combination with various other antioxidants, Irgafos 168, ADK STAB PEP-36, ADK STAB PEP-36A, ADK STAB HP-10, and ADK STAB 1178 are preferred, with ADK STAB PEP-36A and ADK STAB PEP-36 being particularly preferred. These phosphorus-based antioxidants may be used alone or in combination of two or more kinds.

[0082] In addition, examples of the sulfur-based antioxidant as the antioxidant include, but are not limited to, 2,4-bis(dodecylthiomethyl)-6-methylphenol (Irganox 1726, manufactured by BASF), 2,4-bis(octylthiomethyl)-6-methylphenol (Irganox 1520L, manufactured by BASF), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1 ,3-diylbis[3-dodecylthio]propionate] (ADEKA STAB AO-412S, manufactured by ADEKA Corporation), 2,2-bis{[3-(dodecylthio)-1-oxopropoxy]methyl}propane-1,3-diylbis[3-dodecylthio]propionate] (ChemiNox PLS, manufactured by Chemipro Chemical Co., Ltd.), and di(tridecyl) 3,3'-thiodipropionate (AO-503, manufactured by ADEKA Corporation). Among these commercially available sulfur antioxidants, ADK STAB AO-412S and Cheminox PLS are preferred from the viewpoints of the effect of imparting thermal stability to the resin, the effect of using them in combination with various antioxidants, and ease of handling. These sulfur-based antioxidants may be used alone or in combination of two or more kinds.

[0083] The content of the antioxidant may be any amount that provides the effect of improving thermal stability. If the content is excessive, problems such as bleeding out during processing may occur. Therefore, the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, even more preferably 0.8 parts by mass or less, still more preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin.

[0084] --Ultraviolet absorber-- The methacrylic resin composition of the present embodiment may contain an ultraviolet absorber. The ultraviolet absorbent is not particularly limited, but is preferably an ultraviolet absorbent having a maximum absorption wavelength of 280 to 380 nm, and examples thereof include benzotriazole-based compounds, benzotriazine-based compounds, benzophenone-based compounds, oxybenzophenone-based compounds, benzoate-based compounds, phenol-based compounds, oxazole-based compounds, cyanoacrylate-based compounds, and benzoxazinone-based compounds. These ultraviolet absorbents may be used alone or in combination of two or more.

[0085] As the ultraviolet absorber, from the viewpoints of compatibility with the resin and volatility upon heating, in particular, benzotriazole-based compounds and benzotriazine-based compounds having a molecular weight of 400 or more are preferred, and from the viewpoint of suppressing decomposition of the ultraviolet absorber itself due to heating during extrusion processing, benzotriazine-based compounds are particularly preferred.

[0086] The content of the ultraviolet absorber is not particularly limited as long as it does not impair heat resistance, moist heat resistance, thermal stability, and moldability and exerts the effects of the present invention, but is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, more preferably 0.25 to 3 parts by mass, and even more preferably 0.3 to 3 parts by mass, relative to 100 parts by mass of the methacrylic resin. When it is within this range, an excellent balance of ultraviolet absorbing performance, moldability, etc. is achieved.

[0087] --Release agent-- The methacrylic resin composition of the present embodiment may contain a release agent. Examples of the release agent include, but are not limited to, fatty acid esters, fatty acid amides, fatty acid metal salts, hydrocarbon-based lubricants, alcohol-based lubricants, polyalkylene glycols, carboxylates, and hydrocarbon paraffin-based mineral oils. These release agents may be used alone or in combination of two or more.

[0088] The fatty acid ester that can be used as the release agent is not particularly limited, and any of the conventionally known fatty acid esters can be used. Examples of fatty acid esters that can be used include ester compounds of fatty acids having 12 to 32 carbon atoms, such as lauric acid, palmitic acid, heptadecanoic acid, stearic acid, oleic acid, arachic acid, and behenic acid, with monohydric aliphatic alcohols, such as palmityl alcohol, stearyl alcohol, and behenyl alcohol, and polyhydric aliphatic alcohols, such as glycerin, pentaerythritol, dipentaerythritol, and sorbitan; and complex ester compounds of fatty acids, polybasic organic acids, and monohydric aliphatic alcohols or polyhydric aliphatic alcohols. Examples of such fatty acid ester lubricants include cetyl palmitate, butyl stearate, stearyl stearate, stearyl citrate, glycerin monocaprylate, glycerin monocaprate, glycerin monolaurate, glycerin monopalmitate, glycerin dipalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, glycerin monooleate, glycerin dioleate, glycerin trioleate, glycerin monolinoleate, and the like. glycerin monobehenate, glycerin mono 12-hydroxystearate, glycerin di 12-hydroxystearate, glycerin tri 12-hydroxystearate, glycerin diacetomonostearate, glycerin citrate fatty acid ester, pentaerythritol adipic acid stearate, partially saponified montanic acid ester, pentaerythritol tetrastearate, dipentaerythritol hexastearate, and sorbitan tristearate. These fatty acid ester-based lubricants can be used alone or in combination of two or more. Examples of commercially available products include the Rikemal series, Poem series, Rikestar series, and Rikemaster series manufactured by Riken Vitamin Co., Ltd., and the Excel series, Leodor series, Exepar series, and Coconard series manufactured by Kao Corporation, and more specific examples include Rikemal S-100, Rikemal H-100, Poem V-100, Rikemal B-100, Rikemal HC-100, Rikemal S-200, Poem B-200, Rikestar EW-200, Rikestar EW-400, Excel S-95, and Leodor MS-50.

[0089] The content of the release agent may be an amount that can obtain the effect as a release agent, and if the content is excessive, problems such as bleed-out during processing and extrusion failure due to screw slippage may occur, so the content is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, even more preferably 0.8 parts by mass or less, still more preferably 0.01 to 0.8 parts by mass, and particularly preferably 0.01 to 0.5 parts by mass, relative to 100 parts by mass of the methacrylic resin. When the amount is added in the above range, the decrease in transparency due to the addition of the release agent is suppressed, and release failure during injection molding tends to be suppressed.

[0090] --Other thermoplastic resins-- The methacrylic resin composition of the present embodiment may contain a thermoplastic resin other than the methacrylic resin for the purpose of adjusting birefringence or improving flexibility without impairing the object of the present invention. Other thermoplastic resins include, for example, polyacrylates such as polybutyl acrylate; styrene-based polymers such as polystyrene, styrene-methyl methacrylate copolymer, styrene-butyl acrylate copolymer, styrene-acrylonitrile copolymer, and acrylonitrile-butadiene-styrene block copolymer; and further, for example, acrylic rubber particles having a 3-4 layer structure described in JP-A-59-202213, JP-A-63-27516, JP-A-51-129449, JP-A-52-56150, etc.; rubbery polymers disclosed in JP-B-60-17406 and JP-A-8-245854; methacrylic rubber-containing graft copolymer particles obtained by multistage polymerization described in WO 2014-002491; and the like. Among these, from the viewpoint of obtaining good optical properties and mechanical properties, rubber-containing graft copolymer particles having a graft portion on their surface layer made of a composition compatible with styrene-acrylonitrile copolymers and methacrylic resins containing a structural unit (X) having a ring structure in the main chain are preferred. The average particle size of the above-mentioned acrylic rubber particles, methacrylic rubber-containing graft copolymer particles, and rubber polymer is preferably 0.03 to 1 μm, and more preferably 0.05 to 0.5 μm, from the viewpoint of improving the impact strength and optical properties of the molded article obtained from the composition of this embodiment.

[0091] The content of the other thermoplastic resin is preferably 0 to 50 parts by mass, and more preferably 0 to 25 parts by mass, based on 100 parts by mass of the methacrylic resin.

[0092] The methacrylic resin composition used in this embodiment has a glass transition temperature (Tg) of 115 to 160°C from the viewpoint of heat resistance. When the glass transition temperature (Tg) is 115°C or higher, the occurrence of warping and deformation of convex shape is reduced in reliability tests such as high-temperature aging tests, and there is a tendency that no adverse effect occurs on optical properties. On the other hand, when the glass transition temperature (Tg) is 160°C or lower, melt processing at extremely high temperatures can be avoided, thermal decomposition of resins, etc. is suppressed, and a plate-shaped molded product with good appearance tends to be obtained. From the viewpoint of further obtaining the above-mentioned effects, the glass transition temperature (Tg) is preferably 115 to 150°C, more preferably 120 to 145°C, and particularly preferably 120 to 140°C. The glass transition temperature can be measured by the midpoint method in accordance with JIS-K7121, and specifically, can be measured by the method described in the examples described later.

[0093] In order to enhance the transferability of fine convex shapes, it is preferable that the methacrylic resin composition used in the present embodiment has a low viscosity corresponding to the time of injection and a moderately high fluidity. -1In the above, the melt viscosity is 20 to 235 Pa·sec, preferably 20 to 230 Pa·sec, more preferably 30 to 180 Pa·sec, and particularly preferably 50 to 150 Pa·sec. When the melt viscosity is 20 Pa·sec or more, it is easy to control the flow of the resin during injection, and it tends to be easy to mold the desired shape. On the other hand, when the melt viscosity is 235 Pa·sec or less, the resin has good flowability and good processability, and molding defects such as filling defects tend to be less likely to occur. The melt viscosity is a value measured in accordance with JIS-K7199, and specifically, can be measured by the method described in the examples below.

[0094] The methacrylic resin composition used in the present embodiment preferably has a large tensile elongation at break in order to prevent cracking during demolding and resin remaining in the mold. The tensile elongation at break is preferably 1.2% or more, more preferably 1.5% or more, and even more preferably 2.0% or more. The tensile elongation at break is a value measured in accordance with ISO 527, and specifically, can be measured by the method described in the examples described later.

[0095] In order to suppress thermal decomposition during molding, the methacrylic resin composition used in this embodiment preferably has a terminal double bond ratio of 5.0% or less, more preferably 4.0% or less, and even more preferably 3.5% or less. When the terminal double bond ratio of the methacrylic resin composition is within the above range, the yellowness is small, and the occurrence of molding defects such as silver is reduced, so that molded products with good appearance tend to be obtained. The terminal double bond ratio of the methacrylic resin composition can be specifically measured by the method described in the examples described later.

[0096] The methacrylic resin composition contained in the plate-shaped molded product of this embodiment preferably has a weight average molecular weight (Mw) in the range of 90,000 to 170,000, more preferably 95,000 to 160,000, and even more preferably 100,000 to 150,000, as measured by gel permeation chromatography (GPC). When Mw is 90,000 or more, cracks during molding are reduced, and a plate-shaped molded product with good appearance tends to be obtained. On the other hand, when Mw is 170,000 or less, a plate-shaped molded product with good appearance during molding is easily obtained, which has an excellent balance between mechanical strength and fluidity. The weight average molecular weight of the methacrylic resin composition can be measured by the method described in the examples below.

[0097] (Methacrylic resin composition manufacturing method) Examples of the method for producing the methacrylic resin composition of the present embodiment include a method of kneading using a kneading machine such as an extruder, a heating roll, a kneader, a roller mixer, a Banbury mixer, etc. Among these, kneading using an extruder is preferred in terms of productivity. The kneading temperature may be in accordance with the preferred processing temperatures of the polymer constituting the methacrylic resin and other resins to be mixed, and is generally in the range of 140 to 300° C., preferably 180 to 280° C. In addition, it is preferable to provide the extruder with a vent port for the purpose of reducing volatile content. EXAMPLES

[0098] The present invention will be described below with reference to specific examples and comparative examples, but is not limited to these.

[0099] [Raw materials] The raw materials used in the examples and comparative examples described later are shown below.

[0100] [[Monomers that make up methacrylic resins]] Methyl methacrylate (MMA): Asahi Kasei Corporation N-Phenylmaleimide (PMI): Nippon Shokubai Co., Ltd. N-Cyclohexylmaleimide (CMI): Nippon Shokubai Co., Ltd. Styrene: Fujifilm Wako Pure Chemical Industries, Ltd. Methyl 2-(hydroxymethyl)acrylate (MHMA): Combi-Blocks

[0101] [[Organic solvents]] Meta-xylene (mXy): Manufactured by Mitsubishi Gas Chemical Co., Ltd. Methyl isobutyrate: manufactured by Kanto Chemical Co., Ltd. Toluene: Fujifilm Wako Pure Chemical Industries, Ltd.

[0102] [[Polymerization initiator]] 1,1-Di(t-butylperoxy)cyclohexane: NOF Corporation t-Amylperoxy-2-ethylhexanoate: "Luperox 575" manufactured by Arkema Yoshitomi Co., Ltd. t-Amyl peroxyisononanoate: Arkema Yoshitomi Co., Ltd.

[0103] [[Chain transfer agent]] n-Octyl mercaptan: Chevron Phillips Chemical Company n-Dodecyl mercaptan: Fujifilm Wako Pure Chemical Industries, Ltd.

[0104] [[Additives]] Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]: BASF "Irganox 1010" Tris(2,4-di-t-butylphenyl)phosphite: BASF "Irgafos168" Rikemal H-100: manufactured by Riken Vitamin Co., Ltd. - Adeka STAB 2112: Manufactured by ADEKA Corporation · Stearyl phosphate / distearyl phosphate mixture: Sakai Chemical Industry Co., Ltd. · Adeka STAB PEP-36: ADEKA Corporation Octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)-propionate: BASF "Irganox 1076" Monomethylamine: Mitsubishi Gas Chemical Company, Inc. Dimethyl carbonate: Fujifilm Wako Pure Chemical Industries, Ltd. Triethylamine: Fujifilm Wako Pure Chemical Industries, Ltd.

[0105] (Evaluation of properties of methacrylic resins and methacrylic resin compositions) Hereinafter, the methacrylic resin composition The method for measuring the characteristics is described.

[0106] (1) Measurement of glass transition temperature The glass transition temperature of the methacrylic resin composition was measured in accordance with JIS-K7121. A differential scanning calorimeter (DSC8000, manufactured by Perkin-Lumber Japan Co., Ltd.) was used under the condition of a nitrogen gas flow rate of 25 mL / min. The sample was heated from room temperature (23°C) to 200°C at a rate of 10°C / min (first heating), held at 200°C for 5 minutes to completely melt the sample, then cooled from 200°C to 40°C at a rate of 10°C / min, held at 40°C for 5 minutes, and heated again under the above heating conditions (second heating). Among the DSC curves drawn during this period, the intersection point (midpoint glass transition temperature) between the step-like change partial curve during the second heating and a straight line equidistant in the vertical direction from each baseline extension line was measured as the glass transition temperature (Tg) (°C).

[0107] (2) Measurement of melt viscosity Under conditions conforming to JIS-K7199, a twin capillary rheometer (manufactured by ROSAND) was used at a temperature of 270°C and a shear rate of 1000 sec -1 The melt viscosity (Pa·sec) of the methacrylic resin composition was measured using a capillary die with a diameter of 1 mm.

[0108] (3) Measurement of tensile elongation at break The pellets of the methacrylic resin composition were dried at 80 to 100°C for 24 hours, and injection molded using an injection molding machine (Toshiba Machine Co., Ltd., EX-100SX) according to JIS-K6717 to prepare an ISO3167 A-type dumbbell test piece having a thickness of 4.0 mm. A tensile test was performed on this test piece using a low-load universal material testing machine (Instron) according to ISO527 at a measurement temperature of 23°C and a crosshead speed of 5 mm / min. Five measurements were performed, and the chuck elongation at tensile break was measured, and the average value was calculated as the tensile break elongation (%).

[0109] (4) Measurement of terminal double bond ratio In order to measure the terminal double bond ratio of the methacrylic resin composition, dissolution and reprecipitation were carried out as a pretreatment to remove low molecular weight substances. Specifically, 500 mg of pellets of the methacrylic resin composition were weighed and dissolved in 5 mL of chloroform, and then 30 mL of methanol was added to precipitate the polymer. The precipitated polymer was collected and dried for 5 hours in a vacuum dryer at 40°C, and dissolved in CDCl3 to a concentration of 100 mg / mL to prepare an NMR measurement sample. 1 H-NMR was measured, and the terminal double bond ratio (%) was calculated according to the following calculation formula (1) using the integrated intensity of the peaks of the terminal double bonds (resonance frequencies of 5.5 ppm and 6.1 ppm), the integrated intensity of the peak of the methoxy group of the main chain in the MMA unit (resonance frequency of 3.6 ppm), and the number average molecular weight (Mn) of the methacrylic resin composition measured by the method described later.

number

[0110] (5) Measurement of weight average molecular weight and number average molecular weight of methacrylic resin composition The weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin composition were measured using the following apparatus and under the following conditions. Measurement equipment: Tosoh Corporation gel permeation chromatography (HLC-8320GPC) Measurement conditions: Columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were connected in series. Column temperature: 40℃ The developing solvent was tetrahydrofuran, the flow rate was 0.6 mL / min, and 2,6-di-t-butyl-4-methylphenol (BHT) was added as an internal standard at 0.1 g / L. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Sample: 0.02 g of methacrylic resin composition dissolved in 20 mL of tetrahydrofuran Injection volume: 10μL Standard sample for calibration curve: The following ten types of polymethyl methacrylate (PMMA Calibration Kit MM-10, manufactured by Polymer Laboratories) with known monodisperse weight peak molecular weights and different molecular weights were used. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard sample 10 850 Under the above conditions, the RI detection intensity was measured versus the elution time of the methacrylic resin composition. Based on each calibration curve obtained by measuring the standard samples for calibration curve, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin composition were determined.

[0111] (Method of evaluation of molded products) The evaluation methods for the plate-shaped molded products are described below.

[0112] (1) Measurement of the height and pitch of the convex shapes of molded products The plate-shaped molded product was cut in a direction perpendicular to the main surface (thickness direction) and the cross section obtained was observed using a digital microscope (Keyence Corporation, VHX-1000). The height and pitch of the convex shapes formed on the first main surface of the molded product were measured from the obtained observation image, and the average values ​​of the five convex shapes were recorded in Table 1 as height a and pitch b, respectively.

[0113] (2) Measurement of the filling degree of the convex shape of the molded product The cross section obtained by cutting the plate-shaped molded product in the direction perpendicular to the main surface (thickness direction) was observed using a digital microscope (Keyence Corporation, VHX-1000). The height a of the convex shape formed on the first main surface of the molded product was obtained, and the filling degree, defined as the ratio to the depth of the concave shape in the first mold for forming the convex shape, was calculated using the following formula, and the average value of four points was listed in Table 1 as the filling degree value. In practice, a filling degree of 0.92 or more can be judged to be favorable as a molded product to which a convex shape has been transferred. (Filling degree) = (height a of the convex shape of the molded product) / (depth a of the concave shape of the mold)

[0114] (3) Measurement of warpage of molded products The plate-shaped molded product was placed on a metal platen with the first main surface having a convex shape facing up, and the outer periphery of the molded product was evenly divided into four points. The gaps between the molded product and the platen at the four points (points 15a, 15b, 15c, and 15d in Figure 1(A)) were measured with a thickness gauge, and the value at the point with the largest gap (amount of warping) was recorded as the amount of warping (mm) of the molded product. In the case of a molded product having an uneven portion for connection to other parts on the reverse side (second main surface) of the first main surface of the molded product, the product is trimmed so that only the portion that does not include the uneven portion for connection remains, and the cross section is polished with sandpaper before measuring the amount of warping. In practice, in the case of a plate-shaped molded product having the shape shown in Figs. 1 and 3, if the amount of warpage is 0.4 mm or less, it can be determined that this is within a preferable range for the dimensional accuracy of the molded product.

[0115] (4) Evaluation of the appearance of the molded product The plate-shaped molded product was visually observed for uneven gloss on the first main surface due to insufficient filling of the resin on the fine convex shaped surface of the first mold, poor appearance due to waviness on the second main surface, and yellowing. If there are any defective resin filling areas, they can be seen as chipped areas. The waviness of the second main surface can be judged by checking whether a straight line is distorted when a fluorescent lamp housed in a rectangular case with one long side is shone from above and a reflected image is confirmed. The quality of the flat surface can be judged by checking whether a straight line is distorted when the reflected image is confirmed when a fluorescent lamp is shone from above on the second main surface. In addition, the yellowness index (YI) of the molded product measured by the measuring method described below was judged to be less than 7.0 as a state in which yellowing is suppressed, a state in which YI is 7.0 to 10.0 as a state in which yellowing is slightly occurring, and a state in which YI is more than 10.0 as a state in which yellowing is very occurring. The case where neither uneven gloss on the first main surface nor waviness on the second main surface was observed and yellowing of the molded product was suppressed was rated as "A". The case where either uneven gloss on the first main surface, waviness on the second main surface, or yellowing of the molded product was observed was rated as "B". The case where two or more of uneven gloss on the first main surface, waviness on the second main surface, and yellowing of the molded product were observed was rated as "C".

[0116] (5) Measurement of in-plane retardation of molded products The plate-shaped molded product was placed in a petri dish installed on the measurement table of PA-300-L (manufactured by Photonic Lattice Co., Ltd.) so that the first main surface was on the upper surface. Then, a low-viscosity liquid (contact liquid manufactured by Shimadzu Corporation) that has a refractive index close to that of the methacrylic resin used and does not penetrate the methacrylic resin was added to the petri dish so that it was filled up to the top of the convex shape of the molded product, so that the first main surface of the molded product was immersed in the liquid and the liquid surface of the liquid was flat without any height difference. In this state, the in-plane retardation distribution was measured at a wavelength of 520 nm. The average value of the absolute values ​​of the in-plane retardation (Re) in the area where the convex shape was formed (see Figures 1(A) and 3(A)) was calculated and used as the measured value of the retardation (nm). The birefringence value is preferably in a range that does not adversely affect the optical characteristics, and is therefore preferably less than 100 nm in terms of in-plane retardation.

[0117] (6) Projected area of ​​the first principal surface The plate-shaped molded product was placed so that the first main surface was the upper surface, and the area of ​​the planar shape of the first main surface was obtained by observing the first main surface from above, and the projected area (cm 2 ) was decided.

[0118] (7) Measurement of methyl methacrylate (MMA) content in molded products The amount of methyl methacrylate (MMA) contained in the plate-shaped molded product was measured. [Sample preparation] A measurement sample was cut out from the opposite gate of the plate-shaped molded product, 0.36 g of which was precisely weighed, and then 2.5000 g of internal standard solution (0.9100 g of decane dissolved in 70.0000 g of chloroform) was added and thoroughly stirred to dissolve. After dissolution, 20.0000 g of isopropyl alcohol was added, stirred, and then allowed to stand to reprecipitate the copolymer. The supernatant solution was collected and subjected to gas chromatography measurement under the following measurement conditions. [Measurement conditions] Equipment: GC-2025 (Shimadzu Corporation) column Column name: Zebron ZB-1 (Phenomenex) P / N:7HM-G001-11 Length: 30.0mm Inner diameter: 0.32mm ID Film thickness: 0.25μm Column oven conditions Initial temperature: 45℃ (hold for 5 minutes) Heating rate: 20.00℃ / min Final temperature: 300.0℃ (hold for 12.25 minutes) Sample vaporization conditions Vaporization chamber temperature: 210.0℃ Carrier gas: Helium Pressure: 70.1kPa Total flow rate: 93.2mL / min Column flow rate: 2.20 mL / min Linear speed: 71.0cm / sec Purge dose: 3.0mL / min Split ratio: 40 Detector (FID) conditions Detector temperature: 300.0℃ Sampling rate: 40msec Make-up gas: N2 Make-up flow rate: 30.0mL / min H2 flow rate: 40.0mL / min Air flow rate: 400.0mL / min Autosampler Conditions Injection volume: 1.0μL

[0119] (8) Yellowness Index (YI) measurement of molded products The plate-shaped molded product was crushed and dissolved in chloroform for high-performance liquid chromatography (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to prepare a 12% by mass chloroform solution. The solution was placed in a quartz cell with an optical path length of 10 cm to prepare a measurement sample. Thereafter, using a UV-2600 ultraviolet-visible spectrophotometer (manufactured by Shimadzu Corporation), a quartz cell with an optical path length of 10 cm containing chloroform for high-performance liquid chromatography (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was placed as a reference cell, and the 12% by mass chloroform solution was placed as a measurement cell, and the yellowness index (YI) was measured. [Measurement conditions] Measurement value: Transmitted light Measurement range: 0.0~100.0 Wavelength range: 780~360nm Scan Speed: Fast Slit width: 2.0 nm Sampling pitch: 2.0 nm Lighting: C light source Viewing angle: 10°

[0120] Synthesis Example 1 [Methacrylic resin composition A] 318.7 kg of methyl methacrylate (hereinafter referred to as MMA), 35.5 g of N-phenylmaleimide (hereinafter referred to as PMI), 63.7 kg of N-cyclohexylmaleimide (hereinafter referred to as CMI), 0.341 kg of n-octyl mercaptan as a chain transfer agent, and 225.1 kg of meta-xylene (hereinafter referred to as mXy) ​​were weighed out and added to a 1.25 m 3 The mixture was added to a reactor and stirred to obtain a mixed monomer solution. Next, 116.9 kg of mXy was weighed and added to Tank 1 to prepare additional solvent. Furthermore, 104.5 kg of MMA and 85.5 kg of mXy were weighed into Tank 2 and stirred to obtain an MMA solution for further addition. The liquid in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and tank 1 and tank 2 were each bubbled with nitrogen at a rate of 10 L / min for 30 minutes to remove dissolved oxygen. Then, steam was blown into the jacket to raise the solution temperature in the reactor to 125°C, and polymerization was started by adding a polymerization initiator solution in which 0.457 kg of 1,1-di(t-butylperoxy)cyclohexane was dissolved in 2.67 kg of mXy at a rate of 1 kg / hour while stirring at 50 rpm. During polymerization, the solution temperature in the reactor was controlled at 125±2°C by temperature control using the jacket. 30 minutes after the start of polymerization, the addition rate of the polymerization initiator solution was reduced to 0.25 kg / hour, and mXy was further added from tank 1 at 29.24 kg / hour for 3.5 hours. Then, 4 hours after the initiation of polymerization, the addition rate of the polymerization initiator solution was increased to 0.75 kg / hour, and additional MMA solution was added from Tank 2 at 95 kg / hour for 2 hours. Further, 6 hours after the start of polymerization, the addition rate of the polymerization initiator solution was reduced to 0.25 kg / hour, and 7 hours after the start of polymerization, the addition was stopped. After 8 hours had elapsed since the start of polymerization, a polymerization solution containing a methacrylic resin was obtained, to which were added 0.261 kg of Irganox1010 and 0.784 kg of Irgafos168 as antioxidants, and 0.784 kg of Rikemal H-100 as a mold release agent. Next, the obtained polymerization solution was fed to a concentrator consisting of a tubular heat exchanger and a vaporizer previously heated to 250°C, and devolatilization was carried out. The degree of vacuum in the vaporizer was set to 10 to 15 Torr. The resin flowing down the vaporizer was discharged by a screw pump, extruded from a strand die, cooled with water, and pelletized to obtain a methacrylic resin composition A having an N-substituted maleimide structural unit.

[0121] Synthesis Example 2 [Methacrylic resin composition B] A monomer composition consisting of 60.000 mol% methyl methacrylate, 39.998 mol% styrene, and 0.002 mol% t-amylperoxy-2-ethylhexanoate as a polymerization initiator was continuously fed at 1 kg / h to a 10 L complete mixing tank with a helical ribbon blade, and continuous polymerization was performed at an average residence time of 2.5 hours and a polymerization temperature of 150 ° C. The liquid was continuously withdrawn from the bottom so that the liquid level in the polymerization tank was constant, and was fed to a concentrating device consisting of a tubular heat exchanger and a vaporization tank for devolatilization. The vacuum degree of the vaporization tank was set to 10 to 15 Torr. The resin that flowed down the vaporization tank was discharged with a screw pump, extruded from a strand die, pelletized after water cooling, and introduced into a desolvation device to obtain a pellet-shaped methyl methacrylate-styrene copolymer. This copolymer was dissolved in methyl isobutyrate to prepare a 10% by mass methyl isobutyrate solution. 500 parts by mass of this 10% by mass methyl isobutyrate solution of the copolymer and 1 part by mass of 10% by mass Pd / C (manufactured by NE Chemcat Corporation) as a hydrogenation catalyst were charged into a 1000 mL autoclave apparatus, and the mixture was maintained at 200°C and a hydrogen pressure of 9 MPa for 15 hours to hydrogenate the aromatic double bonds of the styrene moiety of the copolymer. The hydrogenation catalyst was removed using a filter, and 0.05 parts by mass of Rikemar H-100 was added to and mixed with the polymer solution, and the mixture was fed to a concentrator consisting of a tubular heat exchanger and a vaporization tank for devolatilization. The vacuum degree of the vaporization tank was set to 10 to 15 Torr. The resin that flowed down the vaporization tank was discharged using a gear pump, extruded from a strand die, cooled with water, and pelletized to obtain a methacrylic resin composition B.

[0122] Synthesis Example 3 [Methacrylic resin composition C] A 30 L reaction kettle equipped with a stirring device equipped with a paddle blade, a temperature sensor, a cooling tube, and a nitrogen inlet tube was charged with 5.0 kg of methyl methacrylate, 1.25 kg of methyl 2-(hydroxymethyl)acrylate, 0.025 parts by mass of n-dodecyl mercaptan as a chain transfer agent relative to 100 parts by mass of the total amount of all monomers, 0.025 parts of ADK STAB 2112, and 6.25 kg of toluene, and the mixture was heated to 105°C with stirring while passing nitrogen through. While refluxing, 0.05 parts by mass of t-amyl peroxy isononanoate was added to the polymerization tank relative to 100 parts by mass of the total amount of all monomers, and 0.1 parts by mass of t-amyl peroxy isononanoate was further added dropwise over 2 hours while polymerization was carried out under reflux at a polymerization temperature of 105 to 110°C, and the polymerization reaction was further carried out for 6 hours. To the obtained polymer solution, 6.3 g of a stearyl phosphate / distearyl phosphate mixture was added, and a cyclization condensation reaction was carried out for 5 hours at 90 to 110° C. Then, 0.10 parts by mass of Rikemal H-100 was added per 100 parts by mass of the total amount of all monomers, and the mixture was stirred and mixed. The resulting polymerization liquid was subjected to a cyclocondensation reaction and devolatilization treatment using a φ42 mm devolatilization extruder equipped with four front vents and one back vent at 120 rpm at a resin amount of 2.2 kg / hour to obtain pellets of methacrylic resin composition C.

[0123] Synthesis Example 4 [Methacrylic resin composition D] Poly(methyl methacrylate) was imidized with monomethylamine using a co-rotating twin-screw extruder to obtain a methacrylic resin composition having a glutarimide structure. A 40mm screw diameter co-rotating twin screw extruder was used, the extruder cylinder temperature was set to 275°C, the screw rotation speed was set to 150 rpm, and polymethyl methacrylate with a weight average molecular weight of 10,8000 containing 0.1 parts by mass of Rikemar H-100 was supplied from the hopper at a rate of 20 kg / hour when the total mass of the polymer was 100 parts by mass, and nitrogen was flowed into the extruder at a flow rate of 200 mL / min. After the resin was melted and filled by the kneading block, 1.8 parts by mass of monomethylamine was injected from the nozzle for 100 parts by mass of the raw resin, and an imidization reaction was carried out. A reverse flight was inserted at the end of the reaction zone (before the vent port) to fill the resin. The by-products and excess monomethylamine after the reaction were removed by reducing the pressure at the vent port to 50 Torr. The resin that came out as strands from the die installed at the extruder outlet was cooled in a water tank and then pelletized with a pelletizer to obtain an imide resin. Next, a 40mm screw diameter co-rotating twin screw extruder was used, the extruder cylinder temperature was set to 255°C, and the screw rotation speed was set to 150 rpm. The obtained imide resin was fed at 20 kg / hr, and the resin was melted and filled by a kneading block. Then, a mixed solution of dimethyl carbonate and triethylamine was injected from a nozzle as an esterification agent to reduce the carboxylic acid group in the resin. Dimethyl carbonate was 3.2 parts by mass and triethylamine was 0.8 parts by mass per 100 parts by mass of imide resin. The by-products and excess dimethyl carbonate after the reaction were removed by reducing the pressure at the vent port to 50 Torr. The resin that came out as strands from the die installed at the extruder outlet was cooled in a water tank and then pelletized with a pelletizer to obtain a methacrylic resin composition D having a glutarimide structure.

[0124] Synthesis Example 5 [Methacrylic resin composition E] Polymerization was carried out in the same manner as in Synthesis Example 1, except that the amount of n-octyl mercaptan as a chain transfer agent was changed to 0.708 kg, to obtain a methacrylic resin composition E.

[0125] Synthesis Example 6 [Methacrylic resin composition F] 291.5 kg of MMA, 44.0 kg of PMI, 104.5 kg of CMI, 0.20 kg of n-octyl mercaptan as a chain transfer agent, and 247.0 kg of mXy were weighed out and placed in a 1.25m 3 The mixture was added to a reactor and stirred to obtain a mixed monomer solution. Then 123.0 kg of mXy was weighed and added to Tank 1. Furthermore, 110.0 kg of MMA and 80.0 kg of mXy were weighed and stirred in tank 2 to prepare a monomer solution for additional addition. The liquid in the reactor was bubbled with nitrogen at a rate of 30 L / min for 1 hour, and tank 1 and tank 2 were each bubbled with nitrogen at a rate of 10 L / min for 30 minutes to remove dissolved oxygen. Thereafter, steam was blown into the jacket to raise the solution temperature in the reactor to 124°C, and while stirring at 50 rpm, a polymerization initiator solution prepared by dissolving 0.35 kg of 1,1-di(t-butylperoxy)cyclohexane in 4.652 kg of mXy was added at a rate of 1 kg / hour to initiate polymerization, and mXy was added from Tank 1 at a rate of 30.75 kg / hour for 4 hours. During the polymerization, the solution temperature in the reactor was controlled at 124±2° C. by temperature regulation using a jacket. Then, between 4 hours and 6 hours later, the monomer solution containing MMA was added from Tank 2 at a rate of 95 kg / hour. Furthermore, the addition rate of the polymerization initiator solution was reduced to 0.25 kg / hour 0.5 hour after the start of polymerization, to 0.75 kg / hour after 4 hours, and to 0.5 kg / hour after 6 hours. Seven hours after the start of polymerization, the addition of the polymerization initiator solution was stopped and the polymerization was continued for a further 3 hours to obtain a polymerization solution containing a methacrylic resin having a ring structural unit in its main chain. To this polymerization solution, 0.83 kg of Adeka STAB PEP-36, 0.28 kg of Irgafos 168, 0.44 kg of Irganox 1076, and 1.10 kg of Rikemal H-100 were added under stirring. Next, the obtained polymerization solution was fed to a concentrator consisting of a tubular heat exchanger and a vaporizer tank preheated to 260°C to carry out devolatilization. The degree of vacuum in the vaporizer tank was set to 10 to 15 Torr. The resin flowing down the vaporizer tank was discharged by a screw pump, extruded from a strand die, cooled with water, and pelletized to obtain a methacrylic resin F having an N-substituted maleimide structural unit.

[0126] (Examples 1 to 3) - Forming of plate-shaped products with a convex shape on one main surface The methacrylic resin composition A obtained in Synthesis Example 1 was used and injection molding was performed with an injection molding machine (α-S250iA, manufactured by Fanuc Corporation). The mold consisted of a mold (first mold) on the side forming a main surface having a triangular pyramidal convex shape with a convex shape height a = 400 μm and a pitch b = 300 μm and a mold (second mold) on the side forming a flat main surface, and a nested mold in which a heater wire was embedded inside the mold near the surface forming each main surface was used and attached to the injection molding machine. After performing a fluorine-based release coating treatment on the surface of the first mold, the mold temperature of the first mold was heated by a heater heating at a temperature increase rate of about 3 ° C. / sec to the maximum temperature Tmax listed in Table 1, and the mold was closed to perform injection molding. After filling the mold with resin at a cylinder temperature of 290 ° C., the mold temperature of the first mold was cooled to the minimum temperature Tmin listed in Table 1 at a temperature decrease rate of about 1.2 ° C. / sec, and after reaching Tmin, cooling was performed for 90 seconds. The runners and gates were removed to obtain a plate-shaped molded product (240 mm long, 230 mm wide, 2.5 mm thick, see Figure 1) with a convex shape on one main surface. The holding pressure was set high at 100 MPa in the first stage to obtain good transfer immediately after injection, and then lowered from the first stage to 30 MPa in the second stage to relieve stress distortion inside the molded product. The evaluation results are shown in Table 1. As is clear from Table 1, the filling degree was 0.98 to 0.99, and extremely excellent results were obtained in Examples 1 to 3. In addition, the warpage and appearance were also good.

[0127] Example 4 Using the methacrylic resin composition B obtained in Synthesis Example 2, molding was performed under the same conditions as in Example 1, except that the cylinder temperature was 280°C, the maximum temperature Tmax of the first mold was 175°C, the minimum temperature Tmin was 60°C, the temperature of the second mold was 108°C, and the first-stage holding pressure was 95MPa. The evaluation results are shown in Table 1.

[0128] Example 5 Using the methacrylic resin composition C obtained in Synthesis Example 3, molding was performed under the same conditions as in Example 1, except that the maximum temperature Tmax of the first mold was 190° C., the minimum temperature Tmin was 60° C., and the temperature of the second mold was 108° C. The evaluation results are shown in Table 1.

[0129] Example 6 Molding was performed under the same conditions as in Example 2, except that the methacrylic resin composition D obtained in Synthesis Example 4 was used. The evaluation results are shown in Table 1.

[0130] Example 7 The methacrylic resin composition E obtained in Synthesis Example 5 was used, and molding was performed under the same conditions as in Example 2, except that a nested mold was used for a plate-shaped molded product (length 270 mm, width 260 mm, thickness 2.5 mm, see FIG. 3) having a convex shape of a quadrangular pyramid trapezoid (140 μm square base, angle between the base and the side surface is 85 degrees) with a convex shape height a = 400 μm and pitch b = 160 μm on one main surface, and the other main surface was flat, and a heater wire was embedded inside the mold near the surface forming each main surface. The evaluation results are shown in Table 1. As is clear from Table 1, Example 7 showed a filling rate of 0.99, and an extremely excellent result was obtained. In addition, the warpage and appearance were also good.

[0131] Example 8 The methacrylic resin composition A obtained in Synthesis Example 1 was used, and molding was performed under the same conditions as in Example 1, except that a nested mold was used for a plate-shaped molded product (length 150 mm, width 150 mm, thickness 2.5 mm) having a triangular pyramidal convex shape with a convex shape height a=400 μm and a pitch b=300 μm on one main surface and a flat main surface on the other side, and a heater wire was embedded inside the mold near the surface forming each main surface. The evaluation results are shown in Table 1.

[0132] Example 9 The methacrylic resin composition A obtained in Synthesis Example 1 was used, and molding was performed under the same conditions as in Example 1, except that the mold was a nested mold for a plate-shaped molded product (length 240 mm, width 230 mm, thickness 2.5 mm) having a triangular pyramidal convex shape with a convex shape height a = 550 μm and a pitch b = 300 μm on one main surface and a flat main surface on the other side, in which a heater wire was embedded inside the mold near the surface forming each main surface, and the cylinder temperature was set to 290 ° C. The evaluation results are shown in Table 1.

[0133] Example 10 Molding was carried out under the same conditions as in Example 9, except that the methacrylic resin composition E obtained in Synthesis Example 5 was used and the cylinder temperature was set to 270° C. The evaluation results are shown in Table 1.

[0134] Comparative Example 1 Molding was performed under the same conditions as in Example 1, except that heating with a heater was not performed and injection was performed at a mold temperature equal to or lower than the glass transition temperature Tg of the methacrylic resin composition A. The evaluation results are shown in Table 1. As a result of the evaluation, it could not be said that the convex shape was transferred sufficiently.

[0135] Comparative Example 2 Molding was performed under the same conditions as in Example 1, except that the cylinder temperature was set to 270° C. and the maximum temperature Tmax of the first mold was set to less than (Tg+40)° C. The evaluation results are shown in Table 1. As a result of the evaluation, the filling degree was 0.83, and the amount of warping of the molded product was large at 0.80 mm, so that the desired molded product could not be obtained.

[0136] Comparative Example 3 Molding was performed under the same conditions as in Example 2, except that injection was performed at a temperature of the second mold lower than (Tmax-90)° C. The evaluation results are shown in Table 1. As a result of the evaluation, the filling degree was found to be good at 0.98, but the warping of the molded product was significant and the desired molded product could not be obtained.

[0137] Comparative Example 4 Molding was performed under the same conditions as in Example 2, except that injection was performed at a temperature of the second mold exceeding (Tmax-65)° C. The evaluation results are shown in Table 1. As a result of the evaluation, the filling degree was good at 0.98, but the molded product had a large warp and the flat side was confirmed to be wavy, so the desired molded product could not be obtained.

[0138] Comparative Example 5 Molding was performed under the same conditions as in Example 3, except for using the methacrylic resin composition F obtained in Synthesis Example 6. The evaluation results are shown in Table 1. As a result of the evaluation, it was confirmed that the filling rate of the first main surface was 0.75, which was insufficient, and the molded product had a large warp amount of 0.90 mm and was yellowed, so the desired molded product could not be obtained.

[0139] Comparative Example 6 Molding was performed under the same conditions as in Example 9, except for using the methacrylic resin composition F obtained in Synthesis Example 6. The evaluation results are shown in Table 1. As a result of the evaluation, it was confirmed that the filling rate of the first main surface was 0.82, which was insufficient, and the molded product had a large warp amount of 1.30 mm and was yellowed, so that the desired molded product could not be obtained.

[0140] Comparative Example 7 Molding was performed under the same conditions as in Example 1, except that the maximum temperature Tmax of the first mold was set to less than (Tg+40)° C. and the temperature of the second mold was changed to 105° C. The evaluation results are shown in Table 1. As a result of the evaluation, it was confirmed that the filling rate of the first main surface was 0.82, which was insufficient, and the amount of warping of the molded product was large at 1.10 mm, making it impossible to obtain the desired molded product.

[0141] Comparative Example 8 Molding was performed under the same conditions as in Example 1, except that a mold (first mold) was used to form a main surface having fine triangular pyramidal convex portions with a height a = 800 μm and a pitch b = 300 μm, and a mold (second mold) was used to form a flat main surface. In addition, since a mold release failure occurred in which part of the fine convex shape remained inside the mold during mold release, measurements were performed on a location where evaluation of the molded product was possible. The evaluation results are shown in Table 1.

[0142] [Table 1]

[0143] The plate-shaped molded products having fine convex portions obtained in Example 1 and Comparative Example 1 were used as light direction changing elements, and their characteristics were evaluated. 5, light incident on an incident surface (main surface behind the main surface having the fine convex portions) 81 of a plate-shaped molded product 8 having fine convex portions at an incident angle of 45 degrees is reflected by an inclined surface 83 that forms an angle of 85 degrees with a bottom surface 82, and then refracted from an inclined surface 84 that forms an angle of 65 degrees with the bottom surface 82 and emitted to the outside. At this time, the light is emitted from the inclined surface 84 at a refraction angle of 64 degrees, so that the light is emitted at an angle of approximately 90 degrees with respect to the incident surface 81. In other words, this is a light direction conversion element that bends light that is incident on the incident surface at an incident angle of 45 degrees to a direction perpendicular to the incident surface. The molded product 8 was placed as shown in Figure 6, and the clarity of the reflected and transmitted images was evaluated as a light direction conversion element. An LED light source 5 (Thorlabs, M530L4) with a collimating lens emitting light of 530 nm and a frosted diffuser plate 6 (Sigma Koki, #240) were placed, and a USAF Target 7 (Edmund, USAF1951 target negative, target area approximately 12 mm) was irradiated from behind. The light of the target image formed by the light passing through the transmission area 71 of the target (see Figure 7) enters the incident surface 81 of the molded article 8 at an incident angle of 45°, and the reflected image (an image formed by the light reflected by the inclined surface 83 and then transmitted through the inclined surface 84) of the light emerging from the convex shaped surface of the molded article 6 (the main surface having the fine convex shaped portion) was photographed by a single-lens reflex camera 9 (E-PL5, manufactured by Olympus) positioned 350 mm away from the incident surface 81 in the perpendicular direction. The reflected image observed when the molded product obtained in Example 1 was used was a clear image, whereas the reflected image observed when the molded product obtained in Comparative Example 1 was used showed distortion and chipping of the target image, and was of low clarity. [Industrial Applicability]

[0144] The plate-shaped molded product produced by the manufacturing method of the present invention has good appearance and dimensional accuracy, and can be suitably used as various optical components such as Fresnel lenses, lenticular lenses, light guide plates, components for aerial displays, diffractive optical elements, anti-reflection sheets, anti-glare sheets, and cell culture sheets. [Explanation of symbols]

[0145] 1, 2: Plate-shaped molded products 11, 21: One of the main surfaces (first main surface) having a fine convex shape 12, 22: the other main surface (second main surface) on which the fine convex shape is not formed 13, 23: Areas where fine convex shapes are formed 14, 24: Convex shape 15a, 15b, 15c, 15d: Measurement points for the amount of warping 5:LED light source 6: Frosted diffuser 7:USAF Target 71:Transparent area 72: Shading area 8: Plate-shaped molded products 81:Incidence plane 82: Bottom 83, 84: Slope 9. SLR camera

Claims

1. A method for producing a plate-shaped molded product, The plate-shaped molded product has a glass transition temperature Tg of 115 to 160°C and a melt viscosity of 270°C, 1000 sec. -1 The adhesive layer is made of a single resin composition having a viscosity of 20 to 235 Pa·sec at 20° C., and has no adhesive interface. One main surface (first main surface) of the plate-like molded product has a plurality of fine convex shapes, and the other main surface (second main surface) is a flat surface, a height a of the convex shape is 0.5 to 700 μm, and a ratio b / a of a pitch b of the convex shape to the height a of the convex shape is 0.1 to 2.0; The plate-shaped molded product has a projected area of ​​the first main surface of 225 cm 2 That's all. The method includes injection molding using a first mold on the side where the first main surface is formed and a second mold on the side where the second main surface is formed, and the maximum temperature Tmax of the first mold is set to (Tg+40)°C to (Tg+70)°C, and the temperature of the second mold is set to (Tmax-90)°C to (Tmax-65)°C. A method for producing a plate-shaped molded product, comprising:

2. The method for producing a plate-shaped molded product according to claim 1, wherein the tensile elongation at break of the methacrylic resin composition is 1.2% or more.

3. The method for producing a plate-shaped molded product according to claim 1 or 2, wherein the first mold is heated and then cooled to set the minimum temperature Tmin of the first mold to (Tg-75) ° C. to (Tg-45) ° C.

4. 3. The method for producing a plate-shaped molded product according to claim 1 or 2, wherein, when the first mold is heated and then cooled, the surface temperature of the first mold is increased at a rate of 1 to 10 ° C. / sec and decreased at a rate of 0.5 to 10 ° C. / sec.

Citation Information

Patent Citations

  • Method and device for injection molding

    JP1988095919A

  • Injection molding method of moldings with biased wall thickness and fine uneven form and moldings with biased wall thickness and fine uneven form

    JP1998080938A

  • Injection molding method of moldings with fine uneven form and moldings with fine uneven form

    JP1998080940A

  • Thin plate-shaped molded item and method for molding the same

    JP1999058476A

  • Die for molding synthetic resin

    JP2010264703A